Effect of magnetic field treatment on the structural and aggregation behavior of gluten, gliadin, and glutenin in potato pulp enriched dough - Jialin Song; Feng Han; Ying Sun; Dongliang Zhang; Shanfeng Chen; Hongjun Li (Innovative Food Science & Emerging Technologies, 2026)

Instant CMQT stabilization coupled UHPLC-MS/MS for the quantification of reduced and total forms of cysteine, homocysteine, and glutathione in blood plasma - Yongyin Zhou; Haizhu Tan; Yingtong Chen; Hongjun Luo; Hui Li; Wenhong Luo; Yingxiu Xiao; Zhexuan Lin (Analytica Chimica Acta, 2026)

A novel two-layered hydroxyapatite-strengthened anammox-partial denitrification/anammox reactor for advanced nitrogen removal : Performance and mechanisms - Shenghao Ji; Hongjun Zhao; Shen Cui; Yujie Chen; Haojie Qin; Kengo Kubota; Jianyong Liu; Yu-You Li (Water Research, 2026)

Shape engineering control of BiOCl/MIL-100(Fe) S-scheme heterojunction: Nanosheets and flower-spherical structures, actual water treatment, and biosafety assessment - Yongrong Li; Yilin Bian; Zhenyu Zhang; Hongjun Zhu (Journal of Environmental Chemical Engineering, 2026)

Reprogramming oily water separation with Janus membranes: From asymmetric fabrication to engineering perspectives - Mingyi Ying; Bisheng Li; Jiaheng Teng; Xiang Cai; Cheng Chen; Leihong Zhao; Hongjun Lin (Journal of Environmental Chemical Engineering, 2026)

Extrusion-induced supramolecular disassembly of rice adjunct starch: governing enzymatic convertibility and fermentable sugar release in mashing - Lijun Jiang; Jialin Song; Mingming Qi; Jian Liu; Chengyi Sun; Bo Wang; Fengling Yue; Miaomiao Sui; Dongliang Zhang; Guihong Zhao; Hongjun Li (Food Chemistry, 2026)

Mass-flow control enhances nitrogen removal in a three-stage partial nitritation, anammox and partial denitrification/anammox system treating food waste digestate: Performance and N2O release characteristics - Shenghao Ji; Shen Cui; Hongjun Zhao; Haojie Qin; Tianyi Zhang; Yu Qin; Jianyong Liu; Yu-You Li (Environmental Research, 2026)

Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

Secondary growth enables post-healing of stress-induced cracks in 2D Zr-MOF membrane for enhanced water purification - Miaomiao Tian; Haochen Shen; Cheng Chen; Libo Zhao; Wei Yu; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

Biofilm ecology in wastewater treatment systems: From microscale ecological insights to macroscale process optimization - Shasha Yuan; Pei Li; Ziyang Xie; Zili Zhou; Zhongbo Zhou; Chao Wang; Die Ling Zhao; Fangang Meng; Hongjun Lin (Critical Reviews in Environmental Science and Technology, 2026)

Mapping the True 3D Architecture: Quantitative Morphological Diversity of Human Hepatic Functional Unit Revealed by Fluorescence Micro-optical Section Tomography - Na Chen; Hongjun Liu; Xiaofeng Mei; Silin Liu; Hongjia Hu; Yunxi Lv; Qi Li; Wei Feng; Yifang Ping; Lu Zheng; Shiwu Dong; Yi Wu (Tissue and Cell, 2026)

Sludge-derived biochar-activated peroxymonosulfate as a waste-to-resource pretreatment for sustainable membrane fouling control: Adsorption-oxidation interplay and thermodynamic insights - Mingjing Xie; Biyan Wang; Jiaqi Liu; Xiao Xu; Hanmin Zhang; Meijia Zhang; Xiang Cai; Leihong Zhao; Bisheng Li; Liguo Shen; Jiaheng Teng; Hongjun Lin (Journal of Cleaner Production, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Environmental pollutants and testicular toxicity in male reproductive health: Basic evidence and translational prospects — A narrative review - Andong Guo; Yi Lu; Ye Guo; Hongjun Li (Reproductive Toxicology, 2026)

Construction of MOF-decorated 3D printed membrane with hierarchical surface functionalization for oil-water separation: Role of interfacial energy barrier - Jingtao Hu; Zhiyu Zhao; Hua Li; Saleem Raza; Ying Liu; Cheng Chen; Wei Yu; Yanchao Xu; Hongjun Lin; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2026)

Polystyrene microplastics induce auditory neurotoxicity in mammals: Integrated multi-omics profiling reveals oxidative damage and synaptic molecular dysregulation - Huanzhi Wan; Jingchun Liu; Xuan Yu; Ting Li; Wenting Yu; Bo Liu; Yingzhao Liu; Yuanyuan Zhang; Shimin Zong; Qingquan Hua; Hongjun Xiao (Journal of Hazardous Materials, 2026)

Associations of prenatal PFAS exposure with offspring neurobehavioral outcomes by maternal folate supplementation and cord blood 5-MTHF levels: a prospective birth cohort study - Susu Wang; Chunping Hu; Xin Liang; Lijun He; Hongjun Shi; Shuhua Yang; Ji Bian; Qianlong Zhang; Junjie Ao; Fei Li (Environmental Research, 2026)

Efficient nutrient removal from low C/N municipal wastewater using a phototrophic biofilm system integrating simultaneous nitrification–denitrification and phosphorus removal (SND) - Qingan Meng; Wei Zeng; Jiayu Zhang; Hongjun Liu; Shuangshuang Li; Yongzhen Peng (Environmental Research, 2026)

Catechol-based synergistic antioxidant nanoplatform for alleviating cisplatin-induced hearing loss - Yunni Tu; Bo Liu; Congshu Feng; Yaqin Tu; Hang Yan; Zilong Chen; Jinghang Li; Youfa Wang; Hongjun Xiao; Lesan Yan (Chemical Engineering Journal, 2026)

Adsorption and ligand-to-metal charge transfer (LMCT)-driven photodegradation of PFOA/PFOS by iron-based materials: Mechanistic insights and environmental risk analysis - Tao Jian; Bisheng Li; Cheng Chen; Leihong Zhao; Xiang Cai; Hongjun Lin; Xiaohong Guan (Critical Reviews in Environmental Science and Technology, 2026)

Ultrasound-targeted cavitation induced tumor vascular normalization and radiotherapy sensitization in breast cancer - Zichao Liu; Huai Yang; Zenan Zhang; Chenke Kuang; Liyong Deng; Yueyong Li; Linyuan Jin; Hongjun Nie; Guihua Wang; Meng Du; Zhiyi Chen (Science China Life Sciences, 2026)

Grain tailoring enables robust high-temperature ferroelectricity in ultrathin Hf1–xZrxO2 films - Haoyu Lu; Yu Li; Liyang Ma; Geng Huangfu; Xuanyu Zhao; Changsong Xu; Hongjun Xiang; Yingfen Wei; Hao Jiang; Qi Liu; Ming Liu (Science Bulletin, 2026)

Dimensional crossover and local strain induced deflection of the spin spiral state in multiferroic NiI2 - Tianxing Jiang; Lianchuang Li; Haiyan Zhu; Hongyu Wang; Junchao Tian; Wenzhao Wang; Weiyi Pan; Haitao Wang; Changlin Zheng; Hongjun Xiang; Changsong Xu; Donglai Feng; et al. (Science Bulletin, 2026)

Form-dependent chloroform adsorption behavior from powdered to sintered carbon - Qing Gao; Zhilong He; Jianjun Cheng; Jingwen Li; Dapeng Zhou; Jiahua Shi; Xiuli Chen; Hongjun Liu (Journal of Environmental Chemical Engineering, 2026)

Soil organic carbon and pH govern the divergent trajectories of organic and inorganic sulfur under long-term fertilization - Haotian Shi; Miao Lei; Shaomin Huang; Hongjun Gao; Lu Zhang; Dongchu Li; Shulan Zhang; Xianlu Yue; Qingxu Ma; Wenju Zhang (Journal of Cleaner Production, 2026)

Opening the window to the solar-driven world of MXenes: Mechanisms, synergistic strategies, and emerging applications for sustainable environmental purification - Xiao Zhang; Yingzi Du; Wenzhe Yu; Mingzhu Zhou; Xiang Cai; Leihong Zhao; Hongjun Lin; Bisheng Li (Critical Reviews in Environmental Science and Technology, 2026)

Dual regulatory role of Penicillium oxalicum and Lolium perenne in bauxite residue soilization: Labile organic carbon dynamics and community assembly - Yufei Zhang; Yifan Jiang; Qishuang Li; Hongjun Dong; Feng Zhu; Xianchao Zhang; Graeme J. Millar; Shiwei Huang; Shengguo Xue (Journal of Environmental Sciences, 2026)

Synergistic mechanism of low-frequency magnetic field on structural and functional benefits from homologous binding of potato protein and purple potato anthocyanins - Fengzhang Lv; Miao Wang; Yingjie Lv; Xin Xu; Yilin Wang; Chengye Ma; Shanfeng Chen; Hongjun Li; Chenjie Wang (Food Chemistry, 2026)

Targeting delivery of shikonin via cryo-shocked tumor cells for non-small cell lung cancer treatment - Huanhuan Huang; Hui Ren; Feiye Liu; Wenyue Lv; Mengzhen Xu; Huiheng Feng; Haoli Liu; Dong Chen; Peng Zhao; Hongjun Li; Jing Qin (Chemical Engineering Journal, 2026)

Seed dispersal drives competition between pair-growing trees: implications for forest community dynamics - Xifu Yang; Haifeng Gu; Guangshun Jiang; Ke Rong; Hongjun Li; Qinghua Zhao; Yanhui Guan; Feifei Yang; Wentao Zhang; Tongzuo Zhang; Zhibin Zhang (Plant Ecology, 2026)

Bidirectional seismic kinematic coupling responses of large-diameter tunnels in sloping sites under Rayleigh waves: Analytical solutions using Green’s functions - Bin Li; Jiguo Liu; Yu Miao; Hongjun He (Tunnelling and Underground Space Technology, 2026)

A synergistic protective network of Polygonatum sibiricum-derived carbon nanoparticles against ethanol-induced and oxidative hepatic injury in HepG2 cells - Hongjun Jiang; Jiaxin Li; Qinxun Zhu; Xiongwei Liu; Xin Wei; Zuhua Wang; Ying Zhou; Tingting Feng (Tissue and Cell, 2026)

Niche-specific and stage-dependent dynamics of microbial assemblages in the macroalgal cultivation system - Zhizhuo Shao; Xin Gao; Yi Sun; Yunlei Zhang; Hongjun Li (Regional Studies in Marine Science, 2026)

Electric-field-modulated charge transfer enables efficient molecular oxygen activation on Bi2MoO6/NaNbO3 type-II heterojunction for broad-spectrum antibiotic degradation - Zhuoran Lin; Mingzhu Zhou; Zeyu Zhou; Xiaoyan Tan; Bisheng Li; Renjie Li; Leihong Zhao; Hongjun Lin (Journal of Environmental Chemical Engineering, 2026)

From energy-limited to substrate-limited: Machine learning reveals the spatially shifting controls on cirque morphology in high Mountain Asia - Jinrong Hu; Fuyuan An; Li Yan; Hongjun Yu; Longfei Gai; Xue Min; Ruiyang Xu (CATENA, 2026)

How sea-land breezes affect ozone in coastal cities: spatial and temporal patterns - Naixiu Sun; Ya-nan Wang; Yu Fei; Lin Wu; Yicheng Yang; Liwei Li; Xueling Yang; Hongjun Mao (Environmental Monitoring and Assessment, 2026)

Quantitative assessment impact of anthropogenic heat flux on global urban evapotranspiration retrieval at multiple temporal scales - Zi Yang; Xin Pan; Hongjun Zhu; Fanggang Li; Xiangjin Meng; Rufat Guluzade; Yuanbo Liu; Suyi Liu; Wen He; Zhenwei Wang; Yingbao Yang (Journal of Hydrology, 2026)

Impact of conservation tillage on maize growth dynamics in black soils of Northeast China through multi-platform remote sensing - Hongjun Liu; Junling Sun; Wei Wan; Shiwen Liu; Jianwei Li; Wei Lv; Zhong Liu (Field Crops Research, 2026)

Improving GLASS AVHRR-derived terrestrial shortwave blue-sky albedo using GLASS MODIS-derived albedo: a global long-term study - Zi Yang; Hongjun Zhu; Jie Yuan; Rufat Guluzade; Xin Pan; Xu Ding; Suyi Liu; Congbao Zhu; Yuqian Li; Longlong Guo; Yingbao Yang (International Journal of Remote Sensing, 2026)

Flow-induced vibration energy harvesting performance enhanced with convergent-acceleration effect - Hongjun Sun; Zeyao Yang; Jinxia Li; Zhen Yang (Ocean Engineering, 2026)

Monsoon and sea-level induced environmental shifts in the Bohai Sea, East Asia during the early-middle Pleistocene - Nanze Liang; Yibing Li; Yan Li; Haifeng Wang; Hongjun Yu; Xingyong Xu; Qiao Su; Xingyu Jiang; Guangquan Chen; Tengfei Fu; Weiwei Chen; Liang Yi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The startup characteristics of a one-stage PNA process under the Fe-free influent condition with iron-containing sludge as inoculum - Yan Guo; Qianqian Li; Hongjun Zhao; Hongzhi Ma; Xiaomin Liu; Jianguo Liu; Tianlong Zheng; Qunhui Wang; Yu-You Li (Journal of Water Process Engineering, 2026)

Dual-function tara gum-based antiscalant with efficient antiscaling and antibacterial activity: Performance and molecular simulation investigation - Liping Xiong; Wei Yu; Xinyi Lu; Zhiyu Zhao; Cheng Chen; Renjie Li; Guanhua Jin; Leihong Zhao; Hongjun Lin; Liguo Shen (Journal of Environmental Chemical Engineering, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Numerical investigation on the vortex-induced vibration of circular cylinder based on Reynolds similarity criterion as well as vibration similarity criterion - Yingmei Li; Hongjun Zhu; Md. Mahbub Alam; Tongming Zhou (Ocean Engineering, 2026)

Construction of metal-free 1D/2D hybrid through engineered structure evolution strategy for boosting photocatalytic hydrogen production - Jiahui Fu; Pingfan Zhang; Lei Wang; Wenli Zhang; Min Zhang; Yun Wang; Chunmei Li; Hongjun Dong (Journal of Water Process Engineering, 2026)

Association between heavy-duty vehicle pollution exposure and cardiovascular disease: A cohort study of middle-aged and elderly adults - Xin Ma; Juan Hao; Jinghua Wang; Yan Li; Xianjia Ning; Hongjun Mao; Ting Wang (Journal of Environmental Sciences, 2026)

New insights into the characteristic flavor formation of Sichuan fermented sausages driven by liquid smoke addition: An integrated study based on microbiomics, flavoromics, and untargeted metabolomics - Dong Zhang; Xinrui Xie; Changlian Yu; Yuwei Liu; Li Yang; Chang Su; Xingzhong Zhang; Hongjun Li; Jie Tang (International Journal of Food Microbiology, 2026)

Novel anti-inflammatory peptides identified from beef tripe by network pharmacology, molecular docking, and in vitro study in RAW264.7 murine macrophages - Xuelian Sun; Zhifei He; Li Yang; Hongjun Li (Food Bioscience, 2026)

PM2.5-bound nitrated and oxygenated PAHs induced lipid metabolism disorder through different target organs - Wanting Liang; Xinting Li; Jing Ding; Hongjun Mao; Ting Wang (Environmental Research, 2026)

Defect-triggered S-scheme heterojunction coupled with single-molecular catalytic centers towards selective photocatalytic CO2 reduction to CO - Keyu Cui; Yujia Wang; Xingjing Zhang; Jiaming Li; Chunbo Liu; Liqiu Zhang; Hongjun Dong; Chunmei Li (Chemical Engineering Journal, 2026)

Bridged nitrogen sites in carbon nitride activated by a low-coordination AuN2 configuration for enhanced CO2 photoreduction - Jia Jia; Bo Hu; Lingxi Zhao; Yixin Wang; Yuhan Zhang; Qingyu Li; Mengya Xiao; Hongjun Dong; Chunmei Li (Chemical Engineering Journal, 2026)

Strength Degradation and Chloride Ion Diffusion Behavior of Concrete Under Simulated Marine Exposure - Shaoping Li; Xiaozhou Zhang; Yaling Zhao; Hongjun Jing; Ping Lyu; Junwei Shan (Journal of Marine Science and Engineering, 2026)
Chloride-induced deterioration is a major threat to the durability of marine concrete structures, especially in tidal and submerged zones. This study simulated these environments by immersing C45 concrete specimens in NaCl solutions (5%, 10%, 15%) under both constant immersion and wet–dry cycles. Compressive strength tests, low-field NMR for pore structure, chloride ion profiling, and SEM-EDS analyses were conducted. A modified chloride diffusion model was developed based on Fick’s second law, incorporating time- and concentration-dependent parameters. The results showed that higher NaCl concentrations and tidal zone exposure significantly accelerated concrete degradation. In the tidal zone, wet–dry cycles led to larger macropore formation, higher chloride penetration, and more severe microstructural damage compared to the submerged zone. Compressive strength initially increased and then declined in high-salinity environments, with strength losses reaching up to 25% under 15% NaCl after 120 days. NMR data confirmed the transformation of micropores and mesopores into macropores, especially in the tidal zone. SEM-EDS analysis revealed decalcification, gypsum formation, and Friedel’s salt accumulation on eroded surfaces. It was determined that chloride ion diffusion behavior in concrete is significantly influenced by the chloride content and diffusion concentration, as well as the exposure zone. The developed model indicates that depth increased over time and with concentration. The proposed diffusion model achieved high fitting accuracy (R2 > 0.97), effectively capturing the effects of erosion age and salt; this makes it a reliable tool for predicting chloride ion ingress in marine concrete, and for supporting service life evaluation and durability design.

System-Level Optimization of AUV Swarm Control and Perception: An Energy-Aware Federated Meta-Transfer Learning Framework with Digital Twin Validation - Zinan Nie; Hongjun Tian; Yijie Yin; Yuhan Zhou; Wei Li; Yang Xiong; Yichen Wang; Zitong Zhang; Yang Yang; Dongxiao Xie; Manlin Wang; Shijie Huang (Journal of Marine Science and Engineering, 2026)
Deep-sea exploration increasingly relies on Autonomous Underwater Vehicles (AUVs) to enable persistent, wide-area surveying in harsh and uncertain environments. In practice, however, deployments are constrained by tight energy budgets and bandwidth-limited, intermittent acoustic links, which complicate mission-level coordination. Moreover, many existing systems treat perception and control as loosely coupled modules, often resulting in redundant sensing, inefficient communication, and degraded overall performance—particularly under heterogeneous sensing modalities and shifting geological conditions. To address these challenges, we propose a hierarchical Federated Meta-Transfer Learning (FMTL) framework that tightly integrates collaborative perception with adaptive control for swarm optimization. The framework operates at three levels: (1) Representation Learning aligns heterogeneous sensors in a shared latent space via a physics-informed contrastive objective, substantially reducing communication overhead; (2) Meta-Learning Adaptation enables rapid transfer and convergence in new environments with minimal data exchange; and (3) Energy-Aware Control realizes closed-loop exploration by coupling Federated Explainable AI (FXAI) with decentralized multi-agent reinforcement learning (MARL) for path planning under energy constraints. Validated in high-fidelity hardware-in-the-loop simulations and a digital-twin environment, FMTL outperforms state-of-the-art baselines, achieving an AUC of 0.94 for target identification. Furthermore, an energy–intelligence Pareto analysis demonstrates a 4.5× improvement in information gain per Joule. Overall, this work provides a physically consistent and communication-efficient blueprint for the optimization and control of next-generation intelligent marine swarms.

In-situ assembly of vertically-grown SnS2 nanosheets on TiO2 microspheres for efficient photocatalytic nitrogen fixation - Huijun Liang; Xinyu Wang; Yuanyuan Ji; Xin Li; Xiang Zhen; Jianxun Dong; Feijian Lou; Hongjun Chen; Zhichao Jia; Huiran Zhou; Xiaobing Wang (Fuel, 2026)

Triatomic-doped MXene based catalyst with sodium alginate encapsulation their molecular and DFT calculation study for efficient photocatalytic removal of disinfected by-product from drinking water - Saleem Raza; Ata Ur Rehman; Zhiyu Zhao; Hua Li; Cheng Chen; Wei Yu; Ying Liu; Yanchao Xu; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2026)

Upcycling industrial waste bischofite to anti-aging agents for asphalt: Macro-properties, micro-characteristics, and statistics-based mechanistic analysis - Hongjun Dong; Zihang Li; Canlin Zhang; Chiara Riccardi; Ting Wang; Peng Jin; Yan Yuan (Chemical Engineering Journal, 2026)

Counter-cation engineering in polyoxovanadate cathodes: Unlocking superior zinc-ion storage stability via NH4+ induced hydrogen bond networks - Tiantian Guan; Chunxi Ren; Kunxuan Li; Yu Zhang; Fan Yang; Lei Wang; Qing Han; Xuejing Qiu; Lingling Xie; Hongjun Chen; Xiaobo Ji; Jianmin Ma; et al. (Chemical Engineering Journal, 2026)

Boron nitride nanosheets via arginine-assisted embedded with phosphomolybdic acid as pesticide carriers for visualization in pest control - Li Hao; Minyan Zhou; Jialin Zeng; Jiechun Lin; Lan Hua; Ziting Yin; Mei Guan; Qiangcheng Zheng; Hongjun Zhou; Xinhua Zhou (Chemical Engineering Journal, 2026)

Particle size–dependent molecular perturbations induced by copper nanoparticles in marine medaka (Oryzias melastigma): an integrated miRNA–mRNA analysis - Pengrui Ren; Peipei Zhang; Jingyuan Shi; Hongbo Li; Ruofei Jin; Hongjun Li (Frontiers in Marine Science, 2026)
Introduction Copper nanoparticles (Cu-NPs) have been increasingly released into marine environments due to their extensive applications, posing potential risks to marine organisms and human health. Although Cu-NPs of different particle sizes exhibit distinct toxicities—largely attributed to variations in specific surface area and Cu 2+ dissolution rates—current physicochemical parameters still fail to fully explain these toxic effects, and the underlying molecular mechanisms remain unclear. Methods This study aimed to investigate the toxic effects and underlying molecular mechanisms of Cu-NPs of different nominal primary diameters (10 nm, 50 nm, and 100 nm) on the marine medaka ( Oryzias melastigma ). Results LC 50 point estimates suggested slightly higher toxicity for smaller Cu-NPs. Integrated miRNAomic and transcriptomic analyses revealed that Cu-NPs-10 exposure markedly activated multiple metabolic pathways, including drug metabolism–cytochrome P450, retinol metabolism, and ascorbate and aldarate metabolism. Cu-NPs-50 exposure primarily affected neurodevelopment and synaptic signaling, with predicted miRNA–mRNA associations including miR-202 with mprip-like and miR-2187 with adgrg2-like . In contrast, Cu-NPs-100 exposure activated inflammation- and barrier repair-related networks, with potential miRNA–mRNA relationships involving miR-202 with tm4sf5 , miR-106a, miR-132c, miR-200b, and miR-202 with znfx1 , as well as miR-2187 and miR-202 with rhbdl2 . Discussion Collectively, the integrated miRNA–mRNA analysis suggests that smaller Cu-NPs show a correlation with more intense molecular stress responses than larger particles under seawater transformations (e.g., aggregation/dissolution), and provides insights into the key regulatory networks potentially underlying these size-associated responses.

Open the door to the new world of singlet oxygen in the peracetic acid system: Generation and identification - Rui Liu; Wen Lu; Yuting Liu; Mingzhu Zhou; Bisheng Li; Hongjun Lin; Jiaheng Teng; Liguo Shen; Xiaohong Guan; Leihong Zhao (Water Research, 2026)

Multiscale thermodynamic insights into membrane fouling control by biochar-activated peroxymonosulfate pretreatment: Synergy of oxidation and adsorption - Mingjing Xie; Wenfa Yang; Xiaoni Zhou; Biyan Wang; Jiaqi Liu; Xiao Xu; Liguo Shen; Hanmin Zhang; Meijia Zhang; Wei Yu; Jiaheng Teng; Hongjun Lin; et al. (Water Research, 2026)

A crack detection system for underwater marine structures based on an improved YOLOv12 model - Hongquan Li; Fei Kang; Xianyu Zhu; Jing Chen; Hongjun Li (Ocean Engineering, 2026)

Urbanization increases the impact of micropollutants on riverine planktonic food web - Bob Adyari; Lanping Zhang; Francisco J.A. Nascimento; Dandan Izabel-Shen; Yiqing Zhang; Meixian Cao; Jianjun Wang; Hongjun Li; Qian Sun; Chang-Ping Yu; Anyi Hu (Journal of Hazardous Materials, 2026)

The structure and performance of polyvinylidene fluoride membranes by using water-soluble polyester as an additive via immersion precipitation phase inversion - Jiaxin He; Shuo Sun; Hongjun Li; Wei Du; Hongwei Zhang; Danying Zuo (Journal of Fluorine Chemistry, 2026)

Electroactivated cobalt-cobalt Prussian blue analog composite membrane for rapid persulfate-driven antibiotic degradation and fouling mitigation - Xiaoyue Yao; Hao Wang; Jingjing Liu; Yu Wang; Xuewen Tang; Hongjun Lin; Leihong Zhao; Bisheng Li; Renjie Li (Chemical Engineering Journal, 2026)

Organic electron donor limitation triggers metabolic trade-offs in anaerobic granular sludge: The pivotal role of Fe-mediated electron bifurcation - Bochuang Huang; Yangyang Li; Jinhao Zhu; Juncong Zou; Dexin Wang; Chunping Yang; Hongjun Han; Wencheng Ma (Chemical Engineering Journal, 2026)

Proline-functionalized zein nano delivery system enables sustained brassinolide release for enhanced salt stress tolerance in cucumber cultivation - Jihao Zuo; Ruopeng Lan; Jinting Cai; Long Chen; Dongyan Yang; Huayao Chen; Li Hao; Ximing Zhong; Xinhua Zhou; Hongjun Zhou (Chemical Engineering Journal, 2026)

Alternating current or direct current: Which is better for electrochemical membrane separation water purification system? - Zhen Qiu; Jiujing Xu; Cheng Chen; Wei Yu; Bisheng Li; Liguo Shen; Bing Yu; Huajun Feng; Hongjun Lin (Chemical Engineering Journal, 2026)

Hydrogen-bonded organic framework enables ultrathin polyamide membrane for efficient endocrine disrupting compounds removal - Jiujing Xu; Xueyu Wang; Cheng Chen; Rukang Jiang; Boya Wang; Bisheng Li; Leihong Zhao; Liguo Shen; Hongjun Lin; Banglin Chen (Chemical Engineering Journal, 2026)

Lacticaseibacillus paracasei subsp. paracasei Q- 1 Exhibits Good Safety and Effectively Prevents Escherichia coli K99-Induced Diarrhea in Mice - Fengjie Wang; Li Chen; Yang Li; Guangping Gao; Yanan Wang; Ruili Shi; Hongjun Zhang; Yingyu Chen; Rui Cao; Qiumei Shi; Tonglei Wu (Probiotics and Antimicrobial Proteins, 2026)

Upper-bound limit analysis of near-fault jointed slopes stability based on the pulse-like ground motion and slope surface concave convex characteristics: a case study - Dejian Li; Hongjun Guo; Junwen Fu; Yingbin Zhang; Qiangshan Yu (Bulletin of Engineering Geology and the Environment, 2026)

Latitude-dependent diversity and assembly processes of coastal microbial communities across multiple trophic levels in the China Seas - Yunlei Zhang; Xin Gao; Zhizhuo Shao; Yi Sun; Zheng Zhang; Hongjun Li; Jinqing Ye (Frontiers in Marine Science, 2025)
Coastal sediment ecosystems function as dynamic interfaces for land-sea interactions, harboring highly complex microbial communities which support vital ecological functions. However, the mechanisms governing microbial diversity maintenance and cross-trophic community assembly at large spatial scales remain poorly explored. In this study, a high-throughput sequencing approach was employed to analyze the bacterial, fungal and protistan communities in surface sediments of the China Seas. As indicated by higher values across most indices, bacterial communities generally exhibited greater richness and alpha diversity compared to fungal and protistan communities. Beta diversity decomposition revealed that species turnover dominated community variations across all three trophic levels, with the highest contribution in bacteria. The neutral community model revealed that stochastic processes exerted a stronger influence on bacterial assembly relative to fungi and protists. Moreover, null model analyses demonstrated that bacterial communities were primarily structured by dispersal limitation, fungal communities by ecological drift, while protistan communities co-regulated by homogeneous selection and homogenizing dispersal. Furthermore, similar latitude-dependent patterns in the α- and β- diversity were observed in bacteria and protists, yet such patterns were distinct for fungi. Finally, based on the correlations between community variations with their assembly mechanisms, regional species pools exerted the strongest influence on bacterial β-diversity, whereas local assembly processes dominated fungal β-diversity. The present study elucidates the trophic-level-dependent assembly rules of coastal microbiomes, thereby establishing a mechanistic foundation for predicting ecosystem responses to global change and informing evidence-based conservation of coastal ecosystems.

A novel magnetically induced Co@NC-modified electrochemical membrane for continuous peroxymonosulfate activation: achieving ultrafast and cost-effective purification with elucidation of mechanism and application potential - Xiaoyue Yao; Renjie Li; Liguo Shen; Leihong Zhao; Hongjun Lin (Water Research, 2025)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Trans-2-decenal inhibits Phytophthora capsici by inducing ROS accumulation and mitochondrial dysfunction - Siyuan Xie; Lanning Wang; Jingkun Lv; Xiang Feng; Siyu Li; Haojie Tan; Chao Wang; Gang Wang; Hongjun Ge; Chun Xiao; Danyu Shen; Daolong Dou (Pesticide Biochemistry and Physiology, 2025)

Enhanced built-in electric field and strong interfacial electronic coupling in 2D/2D BiO2-x/Ti3C2 Schottky heterojunction boost exciton dissociation for sustainable molecular oxygen activation toward 100 % singlet oxygen generation - Chongyang Yang; Song Tian; Yanyan Liu; Liguo Shen; Cheng Chen; Yanchao Xu; Leihong Zhao; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Journal of Environmental Chemical Engineering, 2025)

Facile synthesis of high-performance crystalline zirconium phosphate adsorbents and its ammonium ion intercalation mechanism for next-generation hemodialysis - Jingwen Feng; Jianjun Cheng; Jingwen Li; Susu Jia; Feiping Cao; Jiajin Feng; Dapeng Zhou; Jiahua Shi; Choon-Hong Tan; Hongjun Liu (Journal of Environmental Chemical Engineering, 2025)

Ultrasound-assisted fermentation of doughs enriched with 7S and 11S soy protein fractions: impacts on quality and protein–protein interactions - Feng Han; Ying Sun; Jialin Song; Xin Zhang; Chuangshuo Yan; Yufan Wang; Shanfeng Chen; Chengye Ma; Hongjun Li (Food Research International, 2025)

Enhancement mechanism of low-frequency magnetic field on the gelation and structures of potato protein emulsion gel - Xin Xu; Yilin Wang; Fengzhang Lv; Miao Wang; Ruoyun Yuan; Dongliang Zhang; Chengye Ma; Hongjun Li; Chenjie Wang (Food Chemistry, 2025)

Enzymatically degradable pesticide microcapsules fabricated from zein nanoparticle-stabilized Pickering emulsions for enhanced safety and prolonged crop protection - Long Chen; Huahui Ren; Liang Li; Jihao Zuo; Jinting Cai; Ying Li; Huayao Chen; Li Hao; Hongjun Zhou; Zhanghua Zeng; Xinhua Zhou (Chemical Engineering Journal, 2025)

Transition metal phosphides: Electron buffer agents for selective and durable seawater oxidation - Jing Zhang; Yang Yang; Kaixuan Huo; Zhiqiang Qiao; Zunjian Ke; Nana Li; Dandan Yuan; Jing Gu; Hongjun Wu; Zhida Li (Chemical Engineering Journal, 2025)

Chemical and microbial mechanism governing simultaneous nitrogen and phosphorus removal by anammox-hydroxyapatite granules - Shen Cui; Shenghao Ji; Hongjun Zhao; Tianyi Zhang; Yu-You Li (Chemical Engineering Journal, 2025)

Pulse electrodeposition of graphene/copper composite foils from waste printed circuit board leachate - Yan Sun; Yamin Li; Jingyu Zhang; Hongjun Liu (Chemical Engineering Journal, 2025)

Dynamic Compaction Resistance Model Considering Stone Block Shape Effects - Xiong Bobo; Li Hongjun; Tian Bin; Chen Bofu; Zheng Qian; Li Chen; Zhang Jingkang (Geotechnical and Geological Engineering, 2025)

Deep Learning in Slope Stability Analysis: Evolution, Challenges, and Future Directions - Dejian Li; Zheng Wang; Hongjun Guo; Yingbin Zhang; Xiao Cheng; Qiangshan Yu (Geotechnical and Geological Engineering, 2025)

Molecular insights in outstanding performance of Ca2+ bridging MXene/Sodium alginate composite membranes - Hua Li; Hongjun Lin; Saleem Raza; Zhiyu Zhao; Siyuan Chen; Yue Wang; Qianqian Zeng; Cheng Chen; Wei Yu; Liguo Shen (Water Research, 2025)

Decreased myocardial glucose uptake precedes cardiac dysfunction in hindlimb unloading mice revealed by dynamic 18F-FDG PET imaging - Min Yang; Yifan Qiu; Lei Bi; Jianzhong Xian; Zhijun Li; Jijin Yao; Hongjun Jin (Life Sciences in Space Research, 2025)

Advanced membrane technology for per- and polyfluoroalkyl substances removal: Innovations in membrane materials and hybrid systems - Wei Yu; Jiaheng Teng; Xiang Cai; Liguo Shen; Genying Yu; Bisheng Li; Leihong Zhao; Hongjun Lin (Journal of Environmental Management, 2025)

Characterizations of air pollutants at roadside monitoring stations and traffic emission effects: A case study in Tianjin, China - Fangyuan Zheng; Junxia Gao; Lin Wu; Naixiu Sun; Wentian Xu; Qijun Zhang; Hongjun Mao; Jianfei Peng; Liwei Li; Ning Yang; Bin Liu (Journal of Environmental Sciences, 2025)

Widely targeted metabolomics and GC–IMS reveal flavor and metabolite variations in Rex and Hyla rabbit meat under different cooking methods - Shuyun Liu; Hongjun Li; Bin Wen; Li Yang; Xuelian Sun; Kaitong Lang; Zhifei He (Food Chemistry, 2025)

A source-oriented precise risk assessment of trace metal(loid)s in sediments of the Yangtze River Basin - Kuo Pang; Lu Liu; Junlan Yang; Hongjun Zhao; Wei Hu; Xiaonan Ji; Yali Guo; Min Li (Environmental Pollution, 2025)

Diatomic catalytic sites on MOF-derived architecture towards effective H2 production - Hongjun Dong; Hansong Cheng; Yun Wang; Zuoyi Liu; Deping Wang; Liqiu Zhang; Yangyang Yu; Chunmei Li (Chemical Engineering Journal, 2025)

Double cross-linking architectonics membranes for high-efficiency oil-water separation and the mechanistic investigation - Yue Wang; Hongjun Lin; Siyuan Chen; Hua Li; Zhiyu Zhao; Qianqian Zeng; Cheng Chen; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2025)

Magnesium-enriched biochar as a multifunctional carrier: unlocking productivity and stability in the algal-bacterial symbiosis system - Xiu Zhang; Xiang Cai; Xin Hu; Chenlu Zong; Hongjun Lin; Liguo Shen; Jiaheng Teng; Bisheng Li; Leihong Zhao; Meijia Zhang (Chemical Engineering Journal, 2025)

Magnetically directed interfacial polyamerization of Fe3O4@CdS@CQDs-embedded polyamide nanofiltration membranes with enhanced separation and photocatalytic self-cleaning performance - Erqiao Chen; Zhihao Chen; Zhongting Liu; Mingzhu Zhou; Bisheng Li; Renjie Li; Liguo Shen; Yang Jiao; Hongjun Lin; Yanchao Xu (Chemical Engineering Journal, 2025)

3D-printed super-wetting membranes with in situ grown MOF for efficient oil-water separation - Siyuan Chen; Zhiyu Zhao; Cheng Chen; Wei Yu; Xinchun Lu; Yue Wang; Hua Li; Qianqian Zeng; Hongjun Lin; Leihong Zhao; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2025)

Unveiling the role of N-doped carbon quantum dots in relieving humic acid inhibition and promoting methanogenesis via enhanced electron transfer - Qiang Liu; Mahmoud Mazarji; Yeqing Li; Lu Feng; Hongjun Zhou; Quan Xu; Alastair James Ward; Yajing Wang; Jianping Su; Chunming Xu; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

Homologous non-covalent binding mechanism of potato protein and purple potato anthocyanins: Insights into structural and functional benefits - Fengzhang Lv; Miao Wang; Xin Xu; Yilin Wang; Ruoyun Yuan; Chengye Ma; Shanfeng Chen; Hongjun Li; Chenjie Wang (Innovative Food Science & Emerging Technologies, 2025)

Novel CoMo-LDH integration enhanced permeability and self-cleaning of MXene-based membrane for efficient water treatment - Qianqian Zeng; Zhiyu Zhao; Yue Wang; Siyuan Chen; Hua Li; Cheng Chen; Wei Yu; Jiaheng Teng; Hongjun Lin; Yu Yang; Liguo Shen (Chemical Engineering Journal, 2025)

Stable molecular-bridged graphene oxide membrane with bioinspired hydrophilic water inlets for ultrafast molecular separation - Boya Wang; Cheng Chen; Wei Yu; Jiujing Xu; Bisheng Li; Leihong Zhao; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2025)

Optimization of up-flow velocity enhances the performance of partial denitrification/anammox process in expanded granular sludge bed reactor based on the formation of hydroxyapatite - Shenghao Ji; Shen Cui; Hongjun Zhao; Haojie Qin; Yu Qin; Yujie Chen; Yu-You Li (Chemical Engineering Journal, 2025)

Performance and microbial adaptation of a continuous granular sludge-type nitritation process facing the decreasing temperature condition until 5 ℃ - Hongjun Zhao; Yan Guo; Ze Zhang; Qianqian Li; Xiaona Wang; Yuanyuan Ren; Yu-You Li; Qunhui Wang (Bioresource Technology, 2025)

Insights into synergistic metabolism mechanisms of carbon, nitrogen and phosphorus in Tetrasphaera-dominated partial denitrifying phosphorus removal and anammox (PDPRA) process - Jiayu Zhang; Wei Zeng; Qingan Meng; Hongjun Liu; Yao Lu; Shuangshuang Li; Yongzhen Peng (Water Research, 2025)

Consortia of SQR9 mutant strains containing the luxS gene mutation can maintain higher functional stability than the wild type - Jingjing WANG; Lingxue MENG; Ying ZENG; Xinrui ZHU; Chuanyong TANG; Zhihui XU; Hongjun LIU; Rong LI; Qirong SHEN (Pedosphere, 2025)

Membrane technology for microplastic removal: Microplastic occurrence, challenges, and innovations of process and materials - Zhuoran Lin; Xingyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Wei Yu; Bisheng Li; Leihong Zhao; Mingyi Ying (Chemical Engineering Journal, 2025)

Deciphering the nexus of soluble microbial products (SMPs) and membrane fouling: Roles, mechanisms, and control strategies - Xinyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Jiaheng Teng; Meijia Zhang; Bisheng Li; Leihong Zhao; Die ling Zhao; Cheng Chen (Chemical Engineering Journal, 2025)

Multifunctional regulation of trace tetra-carboxyl additive for stable Zn anodes in aqueous electrolytes - Xi Cheng; Min Sang; Danying Zuo; Jing Xu; Hongjun Li; Hongwei Zhang (Chemical Engineering Journal, 2025)

Mimicking butterflies: Thermal adaptive management material with shape memory Janus arrays - Guangyao Hou; Xinzhi Wang; Henghao Liu; Hongjun Kang; Xin Jia; Yang Li; Wei Qin; Xiaohong Wu (Chemical Engineering Journal, 2025)

Multi-perspective analysis of long-term vehicle emissions under intensive policy updates in China - Wentian Xu; Fangyuan Zheng; Zhouzhi Li; Junxia Gao; Hui Tong; Haomiao Niu; Bin Sun; Zhaoyang Fan; Lin Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2025)

Heat stroke-induced central nervous system injury: Mechanisms and therapeutic perspectives - Wenjun Yang; Zhen Gao; Chengjin Wang; Min Wang; Yuan Cao; Yun Li; Shaoqing Shi; Yiqi Wu; Lu Wang; Hongjun Kang (Journal of Thermal Biology, 2025)

Alternating current electrochemistry for energy-efficient contaminant removal and resource recovery in water treatment: A critical review - Chengyue Yu; Cheng Chen; Mingzhu Zhou; Bisheng Li; Leihong Zhao; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2025)

Rhubarb with Different Cooking Methods Restored the Gut Microbiota Dysbiosis and SCFAs in Ischemic Stroke Mice - Jing Xu; Taotao Liu; Fuzhu Pan; Xuan Ao; Lan Wang; Rixin Liang; Yuxin Lei; Yurong Ding; Miao Yu; Li Li; Hongjun Yang (Molecular Neurobiology, 2025)

Electric vehicle range prediction considering real-time driving factors and battery capacity index - Xinwei Ma; Jiaao Li; Hongjun Cui; Long Cheng; Yanjie Ji; Jianbiao Wang (Transportation Research Part D: Transport and Environment, 2025)

Study on climate suitability for maize and technical implementation strategies under conservation tillage in Northeast China - Hongjun Liu; Wei Wan; Mandi Zheng; Jianwei Li; Shiwen Liu; Wei Lv; Yongxin Zhou; Zhong Liu (Soil and Tillage Research, 2025)

Cu-Thioamide coordination polymers derived Cu-S catalysts for CO2 electroreduction to formate - Honglin Li; Xin Zhang; Yuanyuan Wen; Jingyuan Li; Yu Liu; Hongjun Mao; Hongman Sun; Jingbin Zeng; Zifeng Yan (Fuel, 2025)

Antibacterial properties of folic acid-based hydrogel loaded with CeCDs and its potential application in food preservation - Mengzhen Wang; Li Zeng; Hongjun Chen; Senhao Hu; Chengzhi Huang; Shujun Zhen; Lei Zhan (Food Chemistry, 2025)

Direct visual detection for methicillin-resistant Staphylococcus aureus in milk based on the RPA-Cas12a-LFS method - Yixiang Sun; Liren Zhang; Huimin Wu; Hongjun Chen; Huijie Hu; Chongyu Zhang; Xiaoqiang Li; Yuan Li; Yimai Wang; Liqiang Luo; Yizhi Song (Food Control, 2025)

RBM15-mediated m6A modification of XPR1 promotes the malignant progression of lung adenocarcinoma - Changpeng Sun; Hongjun Guan; Jinjin Li; Yinfeng Gu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Multi-objective optimization of cold plates for suppressing thermal runaway propagation within a lithium-ion battery module - Hongjun Fang; Junhui Gong; Lun Li (Process Safety and Environmental Protection, 2025)

Long-term effects of cropping regimes on soil organic carbon and aggregate stability in a Mollisol of Northeast China - Cuilan LI; Zhiyuan CAO; Mo ZHU; Hongjun GAO; Xiuzhi ZHANG; Ping ZHU; Jinjing ZHANG (Pedosphere, 2025)

Enhancing oil/water emulsion separation with inkjet printed beetle-inspired zeolitic imidazolate framework-67 modified membranes - Xinyu Hu; Hongli Xie; Hao Wang; Liguo Shen; Renjie Li; Hongjun Lin; Leihong Zhao; Genying Yu (Desalination, 2025)

Tea tree oil Pickering emulsions stabilized by sodium lignosulfonate-zein covalent conjugate for fungicide delivery and enhanced control efficacy against peanut sclerotium blight - Jihao Zuo; Yitong Lin; Jiayuan Tian; Jinting Cai; Li Hao; Dongjie Liu; Qin Wang; Gengsheng Xiao; Xinhua Zhou; Hongjun Zhou (Chemical Engineering Journal, 2025)

Hydrogen radical-mediated efficient electrocatalytic N2 reduction by bimetallic sulfides - Nana Li; Jing Zhang; Zhiqiang Qiao; Di Gu; Debin Ji; Zhida Li; Dandan Yuan; Hongjun Wu; Baohui Wang (Chemical Engineering Journal, 2025)

Ensemble predictions of high trophic-level fish distribution and species association in response to climate change in the coastal waters of China - Jiao Wang; Xiaohan Liu; Xiuxia Mu; Hongjun Li; Baoquan Li; Yunlei Zhang (Marine Pollution Bulletin, 2025)

Natural variations in the promoter of ZmDeSI2 encoding a deSUMOylating isopeptidase controls kernel methionine content in maize - Xin Lu; Yuhong Lei; Zhennan Xu; Zixiang Cheng; Meng Liu; Yuxin Tai; Xiaohua Han; Zhuanfang Hao; Mingshun Li; Degui Zhang; Hongjun Yong; Jienan Han; et al. (Molecular Plant, 2025)

A synergistic approach integrating potassium ferrate oxidation with polyacrylamide flocculation to enhance sludge dewatering and its mechanisms - Yansha Zeng; Yue Shen; Hongjun Lin; Qiyin Tan; Jiahao Sun; Liguo Shen; Renjie Li; Yanchao Xu; Jiaheng Teng (Journal of Environmental Management, 2025)

Exploring the regulation of metabolic changes mediated by different combined starter cultures on the characteristic flavor compounds and quality of Sichuan-style fermented sausages - Buzhou Xu; Wenliang Qiu; Yuwei Liu; Fanyi Gong; Qian Liu; Jiaxin Chen; Yong Tang; Chang Su; Jie Tang; Dong Zhang; Hongjun Li (Food Research International, 2025)

Integrally moldable carbon fiber evaporator using a weaving process for efficient and stable solar water desalination - Jinyong Yao; Minyuan Feng; Naidan Zhang; Yongheng Zhou; Haroon A.M. Saeed; Weilin Xu; Jianquan Li; Hongjun Yang (Desalination, 2025)

Membrane fouling behaviors of microplastic in coagulation-ultrafiltration process: Role of surface functional groups - Yue Shen; Tao Jian; Genying Yu; Hongjun Lin; Xiang Cai; Liguo Shen; Zengjian Zhao; Leihong Zhao; Meijia Zhang; Die Ling Zhao; Bisheng Li (Chemical Engineering Journal, 2025)

Unveiling environmental adaptability of magnetite-mediated Feammox system: Multiple pathways identification, metabolic responses and engineering potential analysis - Xiangzhuang Fu; Yangyang Li; Weiwei Huang; Dexin Wang; Chunping Yang; Hongjun Han (Chemical Engineering Journal, 2025)

SIRT3 regulates PFKFB3-mediated glycolysis to attenuate cisplatin-induced ototoxicity both in vivo and in vitro - Wei Tang; Shimin Zong; Peiyu Du; Xuan Yu; Ting Li; Bo Liu; Yu Zhong; Wenyang Lei; Wenting Yu; Hongjun Xiao (Archives of Toxicology, 2025)

Non-exemplar class-incremental learning for continual plant diagnosis - Dasen Li; Zhendong Yin; Yanlong Zhao; Yaqin Zhao; Hongjun Zhang (Crop Protection, 2025)

Risk-based environmental assessment of atmospheric impact in the hydrometallurgical recycling of LFP batteries: A comparative analysis of operational scenarios - Yunbin Sun; Zaohong Zhou; Hongjun He; Qiang Li (Journal of Cleaner Production, 2025)

Glycerol-driven optimization of algae-bacteria symbiosis systems for enhanced lipid production and self-flocculation - Yuwei Zhang; Jiaheng Teng; Jiahui Huang; Liguo Shen; Hongjun Lin; Renjie Li; Xiang Cai; Zeqiong Xu; Meijia Zhang (Journal of Environmental Chemical Engineering, 2025)

Modification mechanism of potato protein by twin-screw extrusion from the perspective of temperature variation - Yilin Wang; Xin Xu; Yuanyuan Feng; Fengzhang Lv; Dongliang Zhang; Chengye Ma; Hongjun Li; Chenjie Wang (Food Chemistry, 2025)

L-cysteine modulates the Maillard reaction: Impacts on PhIP and pyrazine formation - Xiaoran Chu; Pengfei Du; Weiting Wang; Hongjun He; Peng Hu; Yaobo Liu; Min Li; Wenxiang Jiang; A.M. Abd El-Aty (Food Chemistry, 2025)

Effect of ultrasound-assisted phosphates treatment on solubilization and stable dispersion of rabbit Myofibrillar proteins at low ionic strength - Chang Su; Yuxin Huang; Jiaxin Chen; Hongjun Li; Dong Zhang; Yong Tang (Food Chemistry, 2025)

Effect of cooking treatment on protein digestibility, peptide profile and potential bioactive peptides of beef tripe during in vitro gastrointestinal digestion - Xuelian Sun; Zhifei He; Li Yang; Hongjun Li (Food Chemistry, 2025)

Green β-cyclodextrin interlayered crumpled polyamide membranes for effective desalination - Jian Yu; Ling Zhang; Hongguang Sun; Renjie Li; Die Ling Zhao; Liguo Shen; Hongjun Lin; Yang Jiao; Yanchao Xu (Desalination, 2025)

High-Probability Ground Motion Simulation in Maduo County for the Maduo MS7.4 Earthquake in 2021: A Possible Supershear Earthquake - Zongchao Li; Zhiwei Ji; Jize Sun; Hiroe Miyake; Yanna Zhao; Hongjun Si; Mengtan Gao; Yi Ding (Journal of Earth Science, 2025)

O-GlcNAc transferase promotes synaptic assembly independent of catalytic activity in C. elegans - Mengting Wu; Huihui Jiang; Qian Li; Yunhe Liu; Hongjun Zhang; Zhiyong Shao (Journal of Biosciences, 2025)

Microstructural regulation of Ir(III) complexes for enhanced photocytotoxicity in photodynamic cancer therapy - Xiaomeng Liu; Qing Zhang; Jiaqi Li; Zhewen Deng; Senqiang Zhu; Bo Ma; Rui Liu; Hongjun Zhu (Journal of Photochemistry and Photobiology B: Biology, 2025)

The relationship between high-quality development and ecosystem health in China's urban agglomerations - Bin Yang; Xiaohan Ma; Jirong Li; Haochen Yu; Hongjun Sui; Fu Chen; Li Tan (Journal of Environmental Management, 2025)

Enhancing ozone catalytic decomposition through acid treatment of α-MnO2 for improved activity and humidity resistance - Shangchao Xiong; Kai Zhang; Zhenghao Xu; Hongjun Ou; Yuanyuan Zheng; Xi Li; Yue Peng; Xubiao Luo; Junhua Li (Journal of Environmental Sciences, 2025)

Long-term diversified cropping promotes wheat yield and sustainability across contrasting climates: Evidence from China and Switzerland - Zhengjun Yan; Yi Xu; Juncong Chu; Thomas Guillaume; Luca Bragazza; Hongjun Li; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Optimizing nitrogen fertilization and irrigation strategies to balance agroecosystem services in the wheat-maize double cropping system: A 21-year field study - Xinyue Qu; Wei Yao; Huijia Ji; Yi Xu; Rong Jia; Xinjie Chen; Hongjun Li; Antonio Rafael Sánchez-Rodríguez; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Substrate preference triggers metabolic patterns of indigenous microbiome during initial composting stages - Yi Ren; Chen Liu; Jiayu Luo; Xuhui Deng; Daoyue Zheng; Jiahui Shao; Zhihui Xu; Nan Zhang; Wu Xiong; Hongjun Liu; Rong Li; Youzhi Miao; et al. (Bioresource Technology, 2025)

Integrated ecological quality assessment of the sea area adjacent to the Yellow River estuary under multiple pollutants - Wen Li; Jinqing Ye; Xin Gao; Yunlei Zhang; Ying Li; Hongjun Li (Frontiers in Marine Science, 2025)
Estuaries are increasingly threatened by pollutants derived from human activities, which severely impair their water quality, biodiversity, and ecological functions. Therefore, within this context, it is essential to conduct comprehensive and scientifically rigorous assessments of estuarine ecological quality. Taking the Yellow River estuary as a case study, a composite index was here developed to evaluate the impacts of eutrophication and heavy metal pollution on estuarine ecological quality. The Trix eutrophication index and potential ecological risk index revealed significant risks of eutrophication and heavy metal pollution. Redundancy analysis identified that nutrients (NO 2 -N and NO 3 -N) and heavy metals (Cd, Hg, and Cr) were the primary pollutants affecting the composition of dominant macrofauna. Threshold Indicator Taxa Analysis was used to identify indicator species for these pollutants and, based on them, bioindicators capable of reflecting eutrophication and heavy metal pollution levels were then determined. A composite index integrating these bioindicators with other biotic indexes was constructed for comprehensive ecological quality assessment. The results showed that the ecological quality of the estuary was good, with values being even lower in the nearshore area. Structural equation modeling confirmed that estuarine ecological quality was significantly influenced, both directly and indirectly, by multiple pollutants, validating the effectiveness of the composite index as an analytical tool. We argue that integrating bioindicators of major pollutants with other benthic indexes into the developed composite index allows to effectively assess the effects of multiple pollutants on estuarine ecological quality and provide valuable insights for ecosystem management.

A study of tripartite strategies for closed-loop charging infrastructure construction of new energy vehicles in China under the expectation of government withdrawal subsidies - Chengyu Li; Xibin Lu; Yiqing Liu; Zuhui Xia; Xueni Wang; Hongjun Zhao (Journal of Cleaner Production, 2025)

Understanding the anti-browning mechanism and physicochemical properties in potato pulp during the magnetic field processing - Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Xin Zhang; Chuangshuo Yan; Yujian Xie; Dongliang Zhang; Hongjun Li (Food Chemistry, 2025)

Exploring the influence of extruded rice adjunct on wort separation efficiency: A bio-macromolecule degradation perspective - Lijun Jiang; Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Dongliang Zhang; Shifeng Yu; Hongjun Li (Food Chemistry, 2025)

Corrigendum to ‘Exploring the maximum nitrite production rate through the granular sludge-type reactor to match the needs of anammox process realizing efficient nitrogen removal’ [Environ. Res. 255 (2024) 119158] - Hongjun Zhao; Yan Guo; Xiaona Wang; Haishu Sun; Ming Gao; Chuanfu Wu; Shuang Li; Yu-you Li; Qunhui Wang (Environmental Research, 2025)

Impact of flow velocity on growth performance, muscle texture, and nutritional composition in seabass (Lateolabrax maculatus) - Fan Fei; Yingying Fang; Zhiwen Zhu; Xinyu Liu; Ao Li; Jiawen Zhang; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Wensheng Li; Chuanxin Zhang; Baoliang Liu (Aquaculture International, 2025)

Photothermal nano-confinement reactor with bimetallic sites for enhanced peroxymonosulfate activation in antibiotic degradation - Hao Wang; Yuzhen Cao; Bisheng Li; Liguo Shen; Xi-Lin Wu; Renjie Li; Hongjun Lin (Water Research, 2025)

Strengthening peroxymonosulfate activation via cotton-derived carbon: Pathway transformation from radical to non-radical - Runbin Su; Yonglin Ma; Lei Liu; Qiangshun Wu; Du Fu; Yu Li; Hongjun Lin; Xiaoxuan Wei; Muhammad Saboor Siddique; Jianrong Chen; Xi-Lin Wu (Journal of Cleaner Production, 2025)

Versatile electrospun cobalt-doped carbon films for rapid antibiotic degradation - Hao Wang; Yuzhen Cao; Liguo Shen; Xi-Lin Wu; Die ling Zhao; Renjie Li; Hongjun Lin (Journal of Environmental Management, 2025)

Astral-based DIA proteomics explored the flavor enhancement mechanism of Chinese traditional smoked bacon by staphylococcal co-fermentation - Li Yang; Hongjun Li; Han Wu; Xueling Sun; Shuyun Liu; Kaitong Lang; Zhifei He (Food Chemistry, 2025)

Organelle remodeling enhances mitochondrial ATP disruption for blocking neuro-pain signaling in bone tumor therapy - Qianyi Zhang; Hongjun Zhuang; Xiaofei Wen; Yonghui Su; Jiamian Wang; Hao Qin; Jiaqian Wang; Zhaoshui Shangguan; Yiqun Ma; Jian Dong; Bo Tian; Xilei Li (Chemical Engineering Journal, 2025)

Highly responsive cryogel based sensing platform by encapsulating programmed DNA for colorimetric detection of 17β-estradiol - Yujia Guo; Jiaxuan Xiao; Fengxiang Ai; Xiaofeng Yang; Kun Zeng; Yuhan Wang; Xuesong Li; Zhen Zhang; Hongjun Zhao (Analytica Chimica Acta, 2025)

Effect of Photoperiod on Nutritional Quality of Muscle and Lipid Metabolism of Litopenaeus vannamei - Yingying Fang; Fan Fei; Fulu Guo; Chengliang Zhu; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Yan Sun; Chuanxin Zhang; Baoliang Liu (Fishes, 2024)
Photoperiod serves as a significant environmental signal for organisms and plays a critical role in regulating their metabolic processes. This research aimed to investigate the lipid metabolism and nutritional quality of adults Litopenaeus vannamei (wet weight: 11.27 ± 0.73 g, body length: 12.45 ± 0.42 cm) under five photoperiods (0L:24D, 8L:16D, 12L:12D, 16L:8D, and 24L:0D) for 40 days in recirculating water systems (RASs). The 24L:0D group increased lipid metabolism, as indicated by increased lipid metabolism enzyme levels and related gene expression linked to lipogenesis. Additionally, shrimp in the 24L:0D exhibited the highest value of crude fat. The 0L:24D showed a significantly reduced content of crude fat compared with the 8L:16D and 12L:12D. In 24L:0D, the content of total essential amino acids (TEAAs), total hydrolyzed essential amino acids (THEAAs), and total non-essential amino acids (TNEAAs) increased significantly. Similarly, the content of polyunsaturated fatty acids (PUFAs) in 24L:0D was also higher than in other groups. Conversely, 0L:24D resulted in lower metabolic activity and a reduction in PUFA content. In conclusion, prolonging light could benefit shrimp cultivation. This study thoroughly examined the effects of varying photoperiods on muscle quality and lipid metabolism in L. vannamei, providing essential insights for the improvement of indoor aquaculture environments. Provision of light for 24 h improves production but has some adverse effects on animal welfare, so a 16 h light cycle is recommended.

Advancing anaerobic digestion with MnO2-modified biochar: Insights into performance and mechanisms - Yeqing Li; Jinglei Zhang; Xinran Wen; Mahmoud Mazarji; Shuo Chen; Qiang Liu; Shenggeng Zhao; Lu Feng; Gang Li; Hongjun Zhou; Junting Pan (Science of The Total Environment, 2024)

iRainSnowHydro v1.0: A distributed integrated rainfall-runoff and snowmelt-runoff simulation model for alpine watersheds - Yuning Luo; Ke Zhang; Yuhao Wang; Sheng Wang; Nan Wu; Shunzhang Li; Qinuo Zhang; Xinyu Chen; Hongjun Bao (Journal of Hydrology, 2024)

Organic carbon compounds removal and phosphate immobilization for internal pollution control: Sediment microbial fuel cells, a prospect technology - Zhenzhen Hu; Qinqin He; Hongjun Zhao; Lingjun Wang; Yuxin Cheng; Xiaonan Ji; Yali Guo; Wei Hu; Min Li (Environmental Pollution, 2024)

Corrigendum to “Changing conventional blending photocatalytic membranes (BPMs): Focuson improving photocatalytic performance of Fe3O4/g-C3N4/PVDF membranes through magnetically induced freezing casting method” [Chem. Eng. J. 365 (2019) 405–414] - Binrong Li; Minjia Meng; Yanhua Cui; Yilin Wu; Yunlei Zhang; Hongjun Dong; Zhi Zhu; Yonghai Feng; Chundu Wu (Chemical Engineering Journal, 2024)

Enhancing Accuracy in Soil Water Content Measurement: A Modified Dielectric Model Approach - Hongjun Chen; Linze Li; Muhammad Awais; Mukhtar Iderawumi Abdulraheem; Wei Zhang; Vijaya Raghavan; Jiandong Hu (Journal of Soil Science and Plant Nutrition, 2024)

Soil nutrient levels are associated with suppression of banana Fusarium wilt disease - Yifan Cao; Yannan Ou; Nana Lv; Chengyuan Tao; Hongjun Liu; Rong Li; Zongzhuan Shen; Qirong Shen (Soil Ecology Letters, 2024)

Multispectral and hyperspectral image fusion via multi-model deep prior regularization - Hangyu Dai; Hongjun Qu; Jiahao Li; Jinglu Tan; Zhenyu Xu; Ya Guo (International Journal of Remote Sensing, 2024)

Polyimide-multiwalled carbon nanotubes composite as electrochemical sensing platform for the simultaneous detection of nitrophenol isomers - Jianzheng Wang; Chunying Liu; Ziao Di; Jiayu Huang; Hongjun Wei; Minjie Guo; Xiaoliang Yu; Nan Li; Jin Zhao; Bowen Cheng (Chemosphere, 2024)

New insights into the improved contaminants removal in SBR by intermittently weak ultrasound - Jingshen Zhang; Jinlin Wang; Guirong Li; Shengyong Jia; Hongjun Han; Fengchang Wu; Yuanhu Pei (Chemosphere, 2024)

Response of soil gross nitrogen mineralization to fertilization practices in China's uplands - Jun Wang; Yinghua Duan; Guanmo Li; Lu Zhang; Dejin Li; Kailou Liu; Xi'an Cui; Boku Zhou; Hongjun Gao; Xiaori Han; Junyong Ma; Shutang Liu; et al. (Journal of Cleaner Production, 2024)

Activation of peroxymonosulfate by novel magnetically recyclable CoFe2O4/MXene quantum dots composites for rapid degradation of tetracycline: Synergistic performance and mechanisms - Zhenyu Guo; Haiyi Jin; Hongyu Sun; Bisheng Li; Huadong Yu; Die Ling Zhao; Hongjun Lin (Journal of Environmental Management, 2024)

High-efficient synthesis of straw-derived carbon quantum dots for facilitating methanogenic performance in high-load co-digestion of food waste and excess sludge - Qiang Liu; Haoyu Zhang; Haozhen Wang; Shenggeng Zhao; Yeqing Li; Lu Feng; Junting Pan; Hongjun Zhou; Chunming Xu (Chemical Engineering Journal, 2024)

Stimuli-responsive sulfur-containing amino acid functionalized boron nitride nanosheets as nanocarriers via improved adhesion to enhance antibacterial performance against plant diseases - Li Hao; Ziting Yin; Mei Guan; Qiangcheng Zheng; Zitao Feng; Jialin Zeng; Jinhui Wang; Huayao Chen; Jinhao Zhao; Hongjun Zhou; Xinhua Zhou (Chemical Engineering Journal, 2024)

Investigation into the electrolysis performance of a novel directly solar irradiated solid oxide electrolysis cell - Hongjun Wang; Chengzhi Guan; Yue Lu; Qiangqiang Zhang; Xin Li; Haoshen Wang; Khurshida F. Sayfieva (Chemical Engineering Journal, 2024)

Response of food waste anaerobic digestion to the dimensions of micron-biochar under 30 g VS/L organic loading rate: Focus on gas production and microbial community structure - Qiang Liu; Ziyan Sun; Junting Pan; Lu Feng; Hongjun Zhou; Yeqing Li; Gang Li (Chemosphere, 2024)

Divergent chemical compositions of soil organic matter size fractions under long-term amendments across a climate gradient - Fanbo Song; Ning Hu; Yilai Lou; Huimin Zhang; Ping Zhu; Dongchu Li; Hongjun Gao; Shuiqing Zhang; Yidong Wang (Soil and Tillage Research, 2024)

Effects of biochar produced from distiller grains on agronomic performances of sorghum (Sorghum bicolor L.) and greenhouse gas emissions from soil - Hongjun YANG; Suyi ZHANG; Jingyu HU; Jianguo HUANG; Zonghua AO; Xiaoqin WANG; Zhe LI; Xuepin LIAO (Pedosphere, 2024)

Microcellular foaming-derived strong ultra-high molecular weight polyethylene/high-density polyethylene foams for thermally insulating and oil-water separating applications - Xujiang Sun; Guilong Wang; Zhaorui Xu; Jialong Chai; Aimin Zhang; Guoqun Zhao; Shuai Li; Yupeng Wang; Hongjun Jiao (Journal of Environmental Chemical Engineering, 2024)

Unraveling the mechanism of aroma loss during prolonged hot air drying of non-smoked bacon: Insights into aroma compounds generation and retention - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Research International, 2024)

Unraveling the influence of lipids on aroma generation in non-smoked bacon during boiling through untargeted lipidomics analysis - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Bioscience, 2024)

Visualizing of engineered five-helix bundle protein for blocking SARS-CoV-2 variants in live animals - Jianzhong Xian; Zhijun Li; Hongbin Huang; Lei Bi; Zhifeng Guan; Guolong Huang; Min Yang; Zhizeng Gao; Jijin Yao; Zhongzhen Su; Hongjun Jin (Chemical Engineering Journal, 2024)

Recent research progress of MOFs-based heterostructures for photocatalytic hydrogen evolution - Jiaming Li; Jia Jia; Deping Wang; Hongjun Dong; Mingshan Zhu (Chemical Engineering Journal, 2024)

Flotation-assisted electrodeposition process to recover copper from waste printed circuit boards - Yamin Li; Xuehao Wei; Hongjun Liu; Yan Sun (Chemical Engineering Journal, 2024)

Amentoflavone Induces Ferroptosis to Alleviate Proliferation, Migration, Invasion and Inflammation in Rheumatoid Arthritis Fibroblast-like Synoviocytes by Inhibiting PIN1 - Yan Ma; Hongjun Lin; Yunman Li; Zhuoling An (Cell Biochemistry and Biophysics, 2024)

Characteristics, Distribution Patterns, and Classification of Volcanic Reservoirs in the Huanghua Depression, Bohai Bay Basin, China - Jian Huang; Changqian Ma; Shihui Zhang; Muyue Xu; Da Lou; Chongbiao Leng; Mutian Qin; Hongjun Li (Journal of Earth Science, 2024)

Source-to-sink processes and genetic mechanism of progradational and lateral accretion submarine fans in the Qiongdongnan Basin, South China Sea - Congjun Feng; Guozhang Fan; Zhili Yang; Xingzong Yao; Xinglei Song; Weiqiang Li; Hongjun Qu; Qiang Zhang; Xuefeng Wang (Frontiers in Marine Science, 2024)
Submarine fan reservoirs are important accumulation zones for oil, gas, and natural gas hydrates, offering significant potential for hydrocarbon exploration. During the deposition period of the Sanya Formation in the southern part of the Changchang Sag of the Qiongdongnan Basin, a large submarine fan developed. However, the internal structure, source-sink system, and formation mechanism of this fan remain poorly understood, posing significant challenges to exploration in this area. This paper examines the source-to-sink sedimentary processes and deposition of submarine fans, using the Changchang Sag, in the Qiongdongnan Basin in the Northern South China Sea, as an example, which will provide valuable general guidance for deep water oil and gas exploration. Based on the theories of seismic stratigraphy and seismic sedimentology, this paper utilizes techniques such as seismic facies analysis, seismic attribute optimization, paleogeomorphology reconstruction, and source-to-sink sedimentary system analysis to analyze the 3D seismic data of the study area. Research indicates that the Sanya Formation in the Changchang Sag of the Qiongdongnan Basin comprises three depositional units: submarine fan, feeder channel, and Semi-deep marine to deep marine mudstone. The submarine fan is a fan formed by the coupling and convergence of submarine fans sourced from the southwest and southeast. Internally, it is divided into three sub-facies: the proximal fan of the sand-rich submarine fan, the main body of the sand-rich submarine fan lobes, and the distal lobes of the sand-rich submarine fan. The submarine fan sourced from the southwest extends nearly north-south and is primarily fed by sediment transported through three large, banded ancient valleys. The sedimentary filling is characterized by three-phase progradation. The submarine fan sourced from the southeast extends nearly east-west and is primarily fed by sediment transported through a single large, banded ancient valley. The sedimentary filling is characterized by two-phase lateral accumulation. During the deposition period of the Sanya Formation, certain areas of the southern uplift belt were exposed for extended periods and subjected to weathering and erosion. Sediments are transported to large ancient valleys through small supply channels. A large number of sediments were transported to the southern slope of the Changchang sag through the provenance channel system such as large ancient valleys and slope belts and deposited in the center of the sag. These make up a complete system of large ancient uplifts and submarine fan source-to-sink sedimentary systems.The sedimentary model is a lobed submarine fan controlled by semi-restricted ancient valleys and expansive basins.

Rehearsal-based class-incremental learning approaches for plant disease classification - Dasen Li; Zhendong Yin; Yanlong Zhao; Jiqing Li; Hongjun Zhang (Computers and Electronics in Agriculture, 2024)

Nonnegligible contribution of terrigenous sediment inputs from local small watersheds to west regions of the Pearl River Estuary, northern South China Sea shelf - Chenjian He; Tingping Ouyang; Mingkun Li; Shanying Zhu; Mingjie Yu; Shasha Peng; Zhaoyu Zhu; Yunpeng Wang; Hongjun Chen; Chengjing Tian (Marine Geology, 2024)

Insights into in situ surface reconstruction in cobalt perovskite oxides for enhanced catalytic activity - Yanyu Jin; Hongjun Cheng; Qibao Wang; Xiaoqing Liu; Shengpeng Mo; Bin Zhou; Yue Peng; Yu Wang; Wenzhe Si; Junhua Li (Journal of Hazardous Materials, 2024)

The development of an emotion lexicon for spicy food flavor experience - Lina Ren; Risu Na; Siyi Jiang; Darong Chen; Li Zhang; Hongjun Li; Pengfei Han (International Journal of Gastronomy and Food Science, 2024)

Exhaust and evaporative volatile organic compounds emissions from vehicles fueled with ethanol-blended-gasoline - Ruikang Li; Chongzhi Zhong; Yang Ning; Yan Liu; Pengfei Song; Ruiguang Xu; Hongjun Mao (Environmental Pollution, 2024)

Research advances in the function and anti-aging effects of nicotinamide mononucleotide - Min Wang; Yuan Cao; Yun Li; Lu Wang; Yuyan Liu; Zihui Deng; Lianrong Zhu; Hongjun Kang (Journal of Zhejiang University-SCIENCE B, 2024)
Aging and age-related ailments have emerged as critical challenges and great burdens within the global contemporary society. Addressing these concerns is an imperative task, with the aims of postponing the aging process and finding effective treatments for age-related degenerative diseases. Recent investigations have highlighted the significant roles of nicotinamide adenine dinucleotide (NAD + ) in the realm of anti-aging. It has been empirically evidenced that supplementation with nicotinamide mononucleotide (NMN) can elevate NAD + levels in the body, thereby ameliorating certain age-related degenerative diseases. The principal anti-aging mechanisms of NMN essentially lie in its impact on cellular energy metabolism, inhibition of cell apoptosis, modulation of immune function, and preservation of genomic stability, which collectively contribute to the deferral of the aging process. This paper critically reviews and evaluates existing research on the anti-aging mechanisms of NMN, elucidates the inherent limitations of current research, and proposes novel avenues for anti-aging investigations.

Review of utilization of bamboo fiber in asphalt modification: Insights into preparation, performance, reinforcement, and challenges - Haibin Li; Songjiang Liu; Fan Yang; Siyu He; Hongjun Jing; Xiaolong Zou; Zhigang Li; Yanping Sheng (Journal of Cleaner Production, 2024)

New insights into the dominance of mixed fermentation of Staphylococcus cohnii and Staphylococcus saprophyticus in Chinese bacon: Complete genomic and comparative genomic perspectives - Li Yang; Hongjun Li; Han Wu; Xuelian Sun; Shuyun Liu; Dong Zhang; Chang Su; Zhifei He (Food Research International, 2024)

Quantitative proteomic analysis to identify potential biomarkers linked to quality traits of beef tripe from different sources - Xuelian Sun; Zhifei He; Li Yang; Han Wu; Hongjun Li (Food Chemistry, 2024)

Effect of heme proteins on the lipid molecule profile and aroma formation during hot air drying of non-smoked bacon - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Chemistry, 2024)

Exploring the maximum nitrite production rate through the granular sludge-type reactor to match the needs of anammox process realizing efficient nitrogen removal - Hongjun Zhao; Yan Guo; Xiaona Wang; Haishu Sun; Ming Gao; Chuanfu Wu; Shuang Li; Yu-you Li; Qunhui Wang (Environmental Research, 2024)

Quantitative trait locus analysis of gray leaf spot resistance in the maize IBM Syn10 DH population - Lina Cui; Mingfei Sun; Lin Zhang; Hongjie Zhu; Qianqian Kong; Ling Dong; Xianjun Liu; Xing Zeng; Yanjie Sun; Haiyan Zhang; Luyao Duan; Wenyi Li; et al. (Theoretical and Applied Genetics, 2024)

Harnessing key bacteria from suppressive soil to mitigate banana Panama disease - Nana Lv; Mohammadhossein Ravanbakhsh; Shuqin Ling; Yannan Ou; Chengyuan Tao; Hongjun Liu; Rong Li; Zongzhuan Shen; Qirong Shen (Biology and Fertility of Soils, 2024)

Montmorillonite supported nano-silica and Schiff base ligands nanocomposite for agricultural antifungal agent with long-term sterilization ability - Li Man; Huayao Chen; Hongkai Deng; Hongjun Zhou; Li Hao; Xinhua Zhou (Applied Clay Science, 2024)

How temporary disruption of metro service influence metro commuters’ mode shifts during the COVID-19 pandemic? Evidence from Tianjin, China - Xinwei Ma; Shaofan Sun; Lin Li; Mingjia He; Hongjun Cui (Travel Behaviour and Society, 2024)

Exploring potential lipid precursors for aroma formation in non-smoked bacon during hot air drying via untargeted lipidomics and oxidation model - Han Wu; Zhifei He; Li Yang; Hongjun Li (Meat Science, 2024)

Microbiological interpretation of weak ultrasound enhanced biological wastewater treatment – using Escherichia coli degrading glucose as model system - Shengyong Jia; Yanfang Diao; Yingying Li; Jingshen Zhang; Hongjun Han; Guirong Li; Yuanhu Pei (Bioresource Technology, 2024)

Masting promotes transformation from predation to mutualism in an oak-weevil-rodent system - Hongmao Zhang; Hongyu Niu; Michael A. Steele; Liqing Peng; Huimin He; Aoqiang Li; Xianfeng Yi; Hongjun Li; Zhibin Zhang (Science China Life Sciences, 2024)

Spatial heterogeneity plays a vital role in shaping the structure and function of estuarine carbon-fixing bacterial communities - Jianrong Xu; Hongxia Ming; Kaijia Ren; Dongwei Li; Huiling Huang; Jiajie Li; Kuishuang Shao; Hongjun Li; Jingfeng Fan (Marine Environmental Research, 2024)

Contrasting benthic bacterial and fungal communities in two temperate coastal areas affected by different levels of anthropogenic pressure - Zhen Wang; Xiaohan Liu; Xiaocheng Wang; Haining Wang; Yi Sun; Jinyong Zhang; Hongjun Li (Marine Environmental Research, 2024)

Effect of staphylococci fermentation and their synergistic Lactobacillus on the physicochemical characteristics and nonvolatile metabolites of Chinese bacon - Li Yang; Hongjun Li; Han Wu; Shuyun Liu; Zhifei He (Meat Science, 2024)

Optimizing humic acid breakdown and methane production via semiconductor-assisted photo-anaerobic digestion - Qiang Liu; Haoyu Zhang; Shuo Chen; Yeqing Li; Mahmoud Mazarji; Lu Feng; Junting Pan; Hongjun Zhou; Chunming Xu (Chemical Engineering Journal, 2024)

Unveiling long-term combined effect of salinity and Lead(II) on anammox activity and microbial community dynamics in saline wastewater treatment - Wenjun Yin; Yilin Li; Wei Xu; Yibin Bao; Junjie Zhu; Xiaomei Su; Jie Han; Chongjun Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2024)

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

Toxic effect and mechanism of β-cypermethrin and its chiral isomers on HTR-8/SVneo cells - Chaojin Si; Hongjun Yang; Xiaoyan Wang; Qiaoxin Wang; Min Feng; Huayue Li; Yuqi Feng; Jiayuan Zhao; Ying Liao (Pesticide Biochemistry and Physiology, 2024)

Selenium in plants: A nexus of growth, antioxidants, and phytohormones - Sufian Ikram; Yang Li; Chai Lin; Debao Yi; Wang Heng; Qiang Li; Lu Tao; Yu Hongjun; Jiang Weijie (Journal of Plant Physiology, 2024)

An efficient solution based on the synergistic effects of nickel foam in NiFe-LDH nanosheets for oil/water separation - Xinchun Lu; Liguo Shen; Hongjun Lin; Lei Han; Jiarong Du; Cheng Chen; Jiaheng Teng; Bisheng Li; Wei Yu; Yanchao Xu (Journal of Hazardous Materials, 2024)

Enhancing mechanism of extrusion pretreatment on bioconversion of distiller’s grains into microbial protein feed - Chenjie Wang; Yao Liu; Ruoyun Yuan; Ling Xu; Chunhui Xin; Yang Tang; Chengye Ma; Shanfeng Chen; Hongjun Li (Animal Feed Science and Technology, 2024)

Spatiotemporal dynamics of bacterioplankton communities in the estuaries of two differently contaminated coastal areas: Composition, driving factors and ecological process - Weiyue Zhang; Jinqing Ye; Xiaohan Liu; Yunlei Zhang; Jinyong Zhang; Lingyu Shen; Yuan Jin; Jianheng Zhang; Hongjun Li (Marine Pollution Bulletin, 2024)

Experimental investigation on the vortex-induced vibration of a circular cylinder partially covered with moss - Hongjun Zhu; Yingmei Li; Hongtao Hao; Md. Mahbub Alam; Tongming Zhou; Tao Tang (Ocean Engineering, 2024)

Electricity-carbon coupling retail package optimization considering low-carbon benefits of distributed renewable energy - Hongjun Gao; Qianzhen Chen; Shuaijia He; Zhiyuan Tang; Haibo Li; Junyong Liu (Journal of Cleaner Production, 2024)

Advances in synthesis and application of amphoteric polymer-based water treatment agents - Wei Yu; Liping Xiong; Jiaheng Teng; Cheng Chen; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Desalination, 2024)

Tailpipe volatile organic compounds (VOCs) emissions from Chinese gasoline vehicles under different vehicle standards, fuel types, and driving conditions - Peiji Liu; Yajun Wu; Zongxuan Li; Zongyan Lv; Jinsheng Zhang; Yan Liu; Ainan Song; Ting Wang; Lin Wu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2024)

The Middle Miocene lobe-shaped and band-shaped submarine fans in the Lingshui Sag, Qiongdongnan Basin: source-to-sink system, genesis and implication - Xingzong Yao; Congjun Feng; Hongjun Qu; Min Zhang; Daming Li (Acta Oceanologica Sinica, 2024)

New directions on membranes for removal and degradation of emerging pollutants in aqueous systems - Die Ling Zhao; Wangyi Zhou; Liguo Shen; Bowen Li; Hongyu Sun; Qianqian Zeng; Chuyang Y. Tang; Hongjun Lin; Tai-Shung Chung (Water Research, 2024)

Transforming waste brake pads from automobiles into Nano-Catalyst: Synergistic Fe-C-Cu triple sites for efficient fenton-like oxidation of organic pollutants - Fuyuan Qi; Jianfei Peng; Zilu Liang; Jiliang Guo; Jiawei Yin; Ainan Song; Zongxuan Li; Jiayuan Liu; Tiange Fang; Jinsheng Zhang; Lin Wu; Qijun Zhang; et al. (Waste Management, 2024)

Pathogenicity and horizontal transmission evaluation of a novel isolated African swine fever virus strain with a three-large-fragment-gene deletion - Han Gao; Dongdong Di; Qianwen Wu; Jie Li; Xing Liu; Zhiying Xu; Sijia Xu; Chengyu Wu; Lang Gong; Yankuo Sun; Guihong Zhang; Hongjun Chen; et al. (Veterinary Microbiology, 2024)

Synthesis of organic layered double hydroxide from waste bischofite and its application on ageing resistance of asphalt - Canlin Zhang; Hongjun Dong; Ting Wang; Yifei Li; Song Xu; Yun Que; Yu Chen (Fuel, 2024)

Generation of key aroma compounds in fat and lean portions of non-smoked bacon induced via lipid pyrolysis reaction - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Chemistry, 2024)

Long-term Fertilizer Application Induces Changes in Carbon Storage and Distribution, and the Consequent Color of Black soil - Jichao Gao; Lichun Wang; Jiafa Luo; Hongjun Gao; Weiwen Qiu; Qiang Li; Xiuzhi Zhang; Ping Zhu; Chang Peng; Yunfei Jiao; Lingying Xu (Journal of Soil Science and Plant Nutrition, 2024)

Effects of childhood maltreatment and major depressive disorder on functional connectivity in hippocampal subregions - Huiqin Nie; Tong Yu; Yurong Zou; Yuhong Li; Juran Chen; Jinrou Xia; Qianyi Luo; Hongjun Peng (Brain Imaging and Behavior, 2024)

Molecular oxygen activation: Innovative techniques for environmental remediation - Lili Zhou; Yuting Liu; Hao Shi; Yurui Qing; Cheng Chen; Liguo Shen; Mingzhu Zhou; Bisheng Li; Hongjun Lin (Water Research, 2024)

Atomically dispersed dual-atom catalysts: A new rising star in environmental remediation - Xialiang Jiang; Cheng Chen; Junjie Chen; Shuning Yu; Wei Yu; Liguo Shen; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Science of The Total Environment, 2024)

Experimental and numerical investigation on the impact of MS2AF on local scour protection performance - Chenghao Zhu; Qiheng Li; Jianguo Zheng; Hongjun Liu; Peng Yu (Ocean Engineering, 2024)

Tuning microscopic structure of La-MOFs via ligand engineering effect towards enhancing phosphate adsorption - Qinqin He; Hongjun Zhao; Zedong Teng; Yali Guo; Xiaonan Ji; Wei Hu; Min Li (Journal of Environmental Management, 2024)

Staphylococcus inoculation enhances the sensorial attributes of Chinese bacon by coordinating the composition of flavor compounds through amino acid metabolism - Li Yang; Hongjun Li; Han Wu; Shunyun Liu; Zhifei He (Food Research International, 2024)

Seawater intrusion-triggered high fluoride groundwater development on the eastern coast of China - Tengfei Fu; Yushan Fu; Chenzhe Li; Minxing Dong; Chen Qi; Zhenyan Wang; Guangquan Chen; Qiao Su; Xingyong Xu; Hongjun Yu (Environmental Science and Pollution Research, 2024)

Assembly mechanisms of microbial communities in plastisphere related to species taxonomic types and habitat niches - Yi Sun; Hongjun Li; Jinyong Zhang; Haining Wang; Xiaoyu Cui; Xin Gao; Wenwen Qiao; Yuyi Yang (Marine Pollution Bulletin, 2024)

Mxenes for membrane separation: from fabrication strategies to advanced applications - Zhengyi Huang; Die Ling Zhao; Liguo Shen; Hongjun Lin; Cheng Chen; Yanchao Xu; Bisheng Li; Jiaheng Teng; Lei Han; Tai-Shung Chung (Science Bulletin, 2024)

Understanding the degradation mechanisms of cyanide and starch in cassava flour during extrusion processing - Mingming Qi; Jialin Song; Lijun Jiang; Luxia Li; Mei Xu; Yueming Li; Shifeng Yu; Hongjun Li (Innovative Food Science & Emerging Technologies, 2024)

Innovative construction of nano-wrinkled polyamide membranes using covalent organic framework nanoflowers for efficient desalination and antibiotic removal - Baoliang Dai; Yijing Hu; Yidan Ding; Liguo Shen; Renjie Li; Dieling Zhao; Yang Jiao; Yanchao Xu; Hongjun Lin (Desalination, 2024)

Dynamical graph neural network with attention mechanism for epilepsy detection using single channel EEG - Yang Li; Yang Yang; Qinghe Zheng; Yunxia Liu; Hongjun Wang; Shangling Song; Penghui Zhao (Medical & Biological Engineering & Computing, 2024)

The stable operation of nitritation process with the continuous granular sludge-type reactor and microbial community analysis - Hongjun Zhao; Yan Guo; Ze Zhang; Haishu Sun; Xiaona Wang; Shuang Li; Jianbo Liao; Yu-You Li; Qunhui Wang (Chemosphere, 2023)

Effects of triclosan exposure on stem cells from human exfoliated deciduous teeth (SHED) fate - Shiwen Deng; Caifeng Li; Junqi Chen; Zhao Cui; Tong Lei; Hongjun Yang; Peng Chen (Science of The Total Environment, 2023)

Membrane-catalysis integrated system for contaminants degradation and membrane fouling mitigation: A review - Cheng Chen; Lun Lu; Lingya Fei; Jiujing Xu; Boya Wang; Bisheng Li; Liguo Shen; Hongjun Lin (Science of The Total Environment, 2023)

A Cryogenian interglacial source rock in South China: Geochemistry, spatial distribution and organic matter enrichment - Peng Li; Hongjun Qu; Aiguo Wang; Shuo Chen (Precambrian Research, 2023)

Protective and immunomodulatory effects of mesenchymal stem cells on multiorgan injury in male rats with heatstroke - Yuyan Liu; Yun Li; Zihui Deng; Yan Zhao; Rui Yuan; Mengmeng Yang; Lu Wang; Yuan Fang; Dengfeng Ding; Feihu Zhou; Hongjun Kang (Journal of Thermal Biology, 2023)

Dynamic characteristics of net anthropogenic phosphorus input to the upper Yangtze River Basin from 1989 to 2019: Focus on the phosphate ore rich area in China - Junlan Yang; Min Li; Lu Liu; Hongjun Zhao; Wenqing Luo; Yali Guo; Xiaonan Ji; Wei Hu (Journal of Environmental Management, 2023)

Fabrication of a novel acid-resistant nanofiltration membrane with dual-charged functional layer for metal ions recovery - Lu Bai; Zhilu Li; Zhengjun Peng; Youjing Zhao; Hongjun Yang; Min Wang (Journal of Environmental Chemical Engineering, 2023)

Effects of replacement partial sodium chloride on characteristic flavor substances of bacon during storage based on GC×GC-MS and non-targeted metabolomics analyses - Jinggang Ruan; Zhicheng Wu; Jingbing Xu; Yiru Yu; Yong Tang; Xinrui Xie; Jiaxin Chen; Zhaoming Wang; Dong Zhang; Jie Tang; Hongjun Li (Food Chemistry, 2023)

Assembly and phylogenetic analysis of the mitochondrial genome of endangered medicinal plant Huperzia crispata - Yu Cao; Dengpan Yin; Bo Pang; Haibo Li; Qiao Liu; Yufeng Zhai; Nan Ma; Hongjun Shen; Qiaojun Jia; Dekai Wang (Functional & Integrative Genomics, 2023)

The enrichment of more functional microbes induced by the increasing hydraulic retention time accounts for the increment of autotrophic denitrification performance - Sicheng Yuan; Qingbo Zhong; Hongjun Zhang; Wentao Zhu; Weibo Wang; Meng Li; Xinhua Tang; Shiyang Zhang (Environmental Research, 2023)

Atomically dispersed Au confined by oxygen vacancies in Au-θ-Al2O3/Au/PCN hybrid for boosting photocatalytic CO2 reduction driven by multiple built-in electric fields - Chunmei Li; Pingfan Zhang; Fang Gu; Lei Tong; Jizhou Jiang; Yan Zuo; Hongjun Dong (Chemical Engineering Journal, 2023)

N-doped carbon quantum dots enhance anaerobic digestion under light condition: The performances and potential mechanisms - Qiang Liu; Shuo Chen; Haoyu Zhang; Lu Feng; Hongjun Zhou; Junting Pan; Yeqing Li; Chunming Xu (Chemical Engineering Journal, 2023)

In-situ introduction of CePO4 for stabilizing electrocatalytic activity of quasi-MOF with partially missing C≡N skeleton - Shuke Li; Meng Xie; Xiao Zhang; Nana Wang; Ran Wang; Yanchao Xu; Hongjun Lin; Yang Jiao; Jianrong Chen (Chemical Engineering Journal, 2023)

Using automated machine learning techniques to explore key factors in anaerobic digestion: At the environmental factor, microorganisms and system levels - Yi Zhang; Zhangmu Jing; Yijing Feng; Shuo Chen; Yeqing Li; Yongming Han; Lu Feng; Junting Pan; Mahmoud Mazarji; Hongjun Zhou; Xiaonan Wang; Chunming Xu (Chemical Engineering Journal, 2023)

JcSEUSS1 negatively regulates reproductive organ development in perennial woody Jatropha curcas - Jingxian Wang; Xue Bai; Yiqing Su; Hongjun Deng; Li Cai; Xin Ming; Yan-Bin Tao; Huiying He; Zeng-Fu Xu; Mingyong Tang (Planta, 2023)

Deep tillage inhibits microbial species interactions and exhibits contrasting roles in bacterial and fungal assembly - Biao Sui; Li Wang; Hongbin Wang; Xingmin Zhao; Feng Jin; Hongjun Wang; Junjie Guo; Qicheng Xu (Agriculture, Ecosystems & Environment, 2023)

Benthic bacterial communities indicate anthropogenic activity footprints in coastal area under long-term marine spatial planning practice - Yi Sun; Hongjun Li; Daixi Liu; Xiaocheng Wang; Quanming Wang; Xiaoyu Cui; Jingfeng Fan (Acta Oceanologica Sinica, 2023)

A sustainable solution for organic pollutant degradation: Novel polyethersulfone/carbon cloth/FeOCl composite membranes with electric field-assisted persulfate activation - Jing Wang; Hao Wang; Liguo Shen; Renjie Li; Hongjun Lin (Water Research, 2023)

Reservoir operation affects propagation from meteorological to hydrological extremes in the Lancang-Mekong River Basin - Xiaobo Yun; Qiuhong Tang; Jie Wang; Jiabo Li; Yumei Li; Hongjun Bao (Science of The Total Environment, 2023)

Coupled responses of the flow-induced vibration and flow-induced rotation of a rigid cylinder-plate body - Tao Tang; Hongjun Zhu; Qing Xiao; Quanyu Chen; Jiawen Zhong; Yingmei Li; Tongming Zhou (Ocean Engineering, 2023)

Enhanced denitrification performance of granular sludge for the treatment of waste brine from ion exchange resin process - Zhenxiang Pan; Zhongqiang Li; Bizhen Zeng; Liguo Shen; Hongjun Lin (Journal of Environmental Management, 2023)

In-situ characterization of the size distribution of lubricant droplets in rotary compressor - Puyuan Wu; Jun Chen; Paul E. Sojka; Yang Li; Hongjun Cao (International Journal of Refrigeration, 2023)

Nano-wrinkled polyamide membrane preparation via heterogeneous surface-regulated interfacial polymerization for enhanced desalination performance - Zhiwen Li; Yanchao Xu; Liguo Shen; Renjie Li; Yang Jiao; Hongjun Lin; Chuyang Y. Tang (Desalination, 2023)

Innovative role of polyvinylpyrrolidone in tailoring polyamide layer for high-performance nanofiltration membranes - Zhiwen Li; Shuilian Peng; Wentian Zhang; Jianzhen Zhang; Yang Jiao; Renjie Li; Liguo Shen; Hongjun Lin; Yanchao Xu (Desalination, 2023)

Anti-ice-pinning superhydrophobic surfaces for extremely low ice adhesion - Ze Tian; Peixun Fan; Dongyu Zhu; Lizhong Wang; Huanyu Zhao; Changhao Chen; Rui Peng; Daizhou Li; Hongjun Zhang; Minlin Zhong (Chemical Engineering Journal, 2023)

Targeted Energy Metabolomics Combined with Spatial Metabolomics Study on the Efficacy of Guhong Injection Against Cerebral Ischemia Reperfusion - Huanhuan Wang; Zhenkun Li; Guangzhao Cao; Liying Tang; Rui Zhou; Caifeng Li; Jingjing Zhang; Hongwei Wu; Xianyu Li; Hongjun Yang (Molecular Neurobiology, 2023)

Seasonal implications for taxonomic sufficiency to simplify M-AMBI methodology in the coastal area adjacent to a eutrophic estuary - Chenman Yang; Hongjun Song; Yi Sun; Pengfei Xie; Yuan Liu; Hongjun Li (Acta Oceanologica Sinica, 2023)

Moderately delayed maturation of composting promotes the reduction of guild-plant pathogenic fungi within vegetable waste - Zijian Lv; Chengyuan Tao; Jiawei Zhang; Zongzhuan Shen; Dongsheng Wang; Bei Wang; Hongjun Liu; Rong Li (Environmental Science and Pollution Research, 2023)

Carbon quantum dots in-situ relieve humic acids inhibition on methanogens while significantly increasing the abundance of Methanosarcinaceae - Qiang Liu; Yuanting Xu; Yeqing Li; Chengjie Ma; Shuo Chen; Lu Feng; Quan Xu; Junting Pan; Bo Peng; Hongjun Zhou; Chunming Xu (Journal of Cleaner Production, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Clinical, epidemiological, and genotypic characteristics of rotavirus infection in hospitalized infants and young children in Yunnan Province - Hongjun Jiang; Yu Zhang; Xiaoyan Xu; Xiaohan Li; Yi Sun; Xin Fan; Ya Xu; Ting Su; Guiqian Zhang; Ziqin Dian (Archives of Virology, 2023)
Rotaviruses are the most important pathogenic cause of non-bacterial diarrhea in infants and children. Approximately 60% of hospital admissions for acute diarrhea worldwide are caused by rotavirus infection. Rotavirus infection and hospitalization among children in China are a social burden, resulting in economic loss. The prevalence and geographical distribution of rotavirus genotypes is variable, partially due to population migration. Due to the unique geographical conditions and climate in Yunnan Province, several viruses with new genotypes have emerged, and multiple genotypes have become co-epidemic. In this study, rotavirus infection screening and genetic characterization of epidemic strains were performed in 149,492 infants and children admitted to hospitals in six representative prefectures in Yunnan Province between 2019 and 2021. The prevalence of rotavirus infection was 13.39% and was highest in January and lowest in September. G9P[8] was the main epidemic rotavirus genotype. Other epidemic genotypes included G2P[4], G8P[8], G9P[4], G2P[8], G3P[8], G4P[8], G3P[4], and G4P[6]. Phylogenetic analysis revealed that locally epidemic strains were influenced by importation of strains from neighboring provinces and other Asian countries. These findings provide a scientific basis for rotavirus prevention and control and lay a foundation for preliminary studies to establish a rotavirus surveillance network in Yunnan Province.

Identification of multi-component metal ion mixtures in complex systems using fluorescence sensor arrays - Hui Meng; Ying Wang; Ruoxi Wu; Yumo Li; Dali Wei; Mingwei Li; Nuanfei Zhu; Fang Zhu; Zhen Zhang; Hongjun Zhao (Journal of Hazardous Materials, 2023)

Breaking the cost barrier: polydopamine@NixCo100-x nanotubes as efficient photocatalysts for organic pollutant degradation - Qianqian Zeng; Hongjun Lin; Yang Qu; Zhengyi Huang; Ning Kong; Lei Han; Cheng Chen; Bisheng Li; Jiaheng Teng; Yanchao Xu; Liguo Shen (Journal of Cleaner Production, 2023)

Initiation and evolution of an isolated submarine canyon system on a low-gradient continental slope - Wei Li; Shuang Li; Tiago M. Alves; Song Jing; Hongjun Chen; Wenhuan Zhan (Geomorphology, 2023)

A novel flower-like nickel-metal-organic framework (Ni-MOF) membrane for efficient multi-component pollutants removal by gravity - Lei Han; Jing Ma; Hongjun Lin; Cheng Chen; Jiaheng Teng; Bisheng Li; Dieling Zhao; Yanchao Xu; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2023)

Enhanced activity of enzyme encapsulated in hydrophilic metal-organic framework for biosensing - Daohan Ge; Mingwei Li; Dali Wei; Nuanfei Zhu; Ying Wang; Mengfan Li; Zhen Zhang; Hongjun Zhao (Chemical Engineering Journal, 2023)

Identification of monoclonal antibody targeting epitope on p72 trimeric spike of African swine fever virus - Xulai Duan; Yingnan Liu; Zongyan Chen; Zhenhua Xie; Chuanwen Tian; Yao Li; Lu Lv; Rongrong Wang; Jingyi Liu; Hongjun Chen (Virus Genes, 2023)

Effect of the random distribution of gravel particles on the mechanical behaviors of conglomerate - Jun Wei; Hualin Liao; Bin Huang; Ning Li; Hongjun Liang; Bo Zhou; Quan Zhang; Long Chen; Hui Feng (Arabian Journal of Geosciences, 2023)

Efficient oily wastewater treatment by a novel electroflotation-membrane separation system consisting a Ni-Cu-P membrane prepared by electroless nickel plating - Jing Wang; Binghong Chen; Hongjun Lin; Renjie Li (Science of The Total Environment, 2023)

Experimental study of the lubricant-refrigerant flow in a rotary compressor - Puyuan Wu; Jun Chen; Paul E. Sojka; Yang Li; Hongjun Cao (International Journal of Refrigeration, 2023)

Volatile compounds comparison and mechanism exploration of non-smoked traditional Chinese bacon in Southwestern China and Eastern China - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Research International, 2023)

Turmeric carbon quantum dots enhanced chitosan nanocomposite films based on photodynamic inactivation technology for antibacterial food packaging - Fangzhou Wen; Peiyuan Li; Hongjun Yan; Wei Su (Carbohydrate Polymers, 2023)

Novel mesocellular silica foam supported poly(amidoxime-ethyleneimine) network for fast and highly efficient uranium extraction from seawater - Jiajia Yang; Yun Li; Tian Tian; Haitao Shi; Zia Ahmad; Ningbo Geng; Jing Jin; Yanqiang Huang; Haijun Zhang; Hongjun Fan; Jiping Chen (Chemical Engineering Journal, 2023)

3D Pore-Throat Microstructure Complexity of Igneous Reservoir Rock and its Effects on the Porosity–Permeability Relation - Mutian Qin; Shuyun Xie; Hongjun Li; Da Lou; Tianfu Zhang; Emmanuel John M. Carranza; Zhiwei Kuang (Natural Resources Research, 2023)

Abundance and Distribution of Macro- and Mesoplastic Debris on Selected Beaches in the Northern Strait of Malacca - Er Vin Lim; Nithiyaa Nilamani; Norhanis M. Razalli; Shoufeng Zhang; Hongjun Li; Muhammad Lutfi Haron; Anisah Lee Abdullah; Zulfigar Yasin; Norlaila Mohd Zanuri; Aileen Tan Shau Hwai (Journal of Marine Science and Engineering, 2023)
Plastics account for 60–80% of marine debris worldwide, and, in 2021, Malaysia was the 28th largest plastic polluter in the world. In light of this finding, the Malaysian government has launched the Roadmap Towards Zero Single-Use Plastics 2018–2030 and the Plastics Sustainability Roadmap 2021–2030 to reduce plastic pollution and implement a circular economy for Malaysia. A comprehensive database of the status of plastic pollution in Malaysia is needed to achieve this target. This study aims to record the presence of macro- (>2.5 cm) and mesoplastic (0.5–2.5 cm) debris at selected beaches in the northern Strait of Malacca. All study sites are publicly accessible beaches (Pulau Songsong, Teluk Aling, and Pulau Gazumbo) except Pulau Lembu, which is in a Marine Protected Area (MPA). The debris was collected from predetermined transects on the beach and categorised according to its form and economic market segments in Malaysia. Most of the macro- (53–75% of total mass) and mesoplastics (52–80% of the total number) were accumulated in the backshore area. Public beaches such as Pulau Gazumbo and Pulau Songsong recorded the highest abundance of macroplastics, with 7.32 g/m2 and 9.77 g/m2, respectively. Teluk Aling recorded the lowest abundance of macroplastics (3.58 g/m2) but the highest in mesoplastics (0.55 items/m2). Most of the macroplastics found were packaging plastics such as plastic bottles, containers, and polystyrene foam debris. Although Pulau Lembu is an MPA, the amount of macroplastics found was considerably high (7.17 g/m2). Based on the beach cleanliness index, Pulau Gazumbo (−3.99) was the dirtiest site, followed by Pulau Lembu (−2.92) and Pulau Songsong (−2.85), while Teluk Aling (−1.63) was the cleanest site, which can explain the amount of macroplastic debris found. However, all the study sites’ cleanliness may not be ideal, as the indexes were less than zero due to the low availability of waste bins and insufficient frequency of beach cleaning. This may not be able to curb the effects of high anthropogenic activities conducted in addition to uncontrollable natural factors.

Modification mechanism of protein in rice adjuncts upon extrusion and its effects on nitrogen conversion during mashing - Lijun Jiang; Jialin Song; Mingming Qi; Wenjing Suo; Yuxin Deng; Yao Liu; Luxia Li; Dongliang Zhang; Chenjie Wang; Hongjun Li (Food Chemistry, 2023)

Reveal the major factors controlling quinolone adsorption on mesoporous carbon: Batch experiment, DFT calculation, MD simulation, and machine learning modeling - Hongjun Zhao; Yitao Lyu; Jingrun Hu; Min Li; Huan Chen; Yi Jiang; Moran Tang; Yang Wu; Weiling Sun (Chemical Engineering Journal, 2023)

Distinct ecological mechanisms drive the spatial scaling of abundant and rare microbial taxa in a coastal sediment - Xia Liu; Hongjun Li; Wen Song; Qichao Tu (Journal of Biogeography, 2023)
Aim Revealing the ecological mechanisms driving the diversity patterns of microbial communities across space and through time is an essential issue in microbial biogeography. This study links microbial spatial scaling with ecological mechanisms, aiming to provide novel mechanistic insights into the biogeographic patterns followed by different types of microbes. Location Beibu Gulf, a semi‐enclosed oceanic bay located on the southern coast of China. Taxon Bacteria, which were further classified as abundant and rare taxa. Methods By employing high throughput sequencing, two typical spatial scaling models, diversity‐area (DAR) and distance‐decay relationships (DDR), were investigated for the abundant and rare microbial communities in a coastal sediment ecosystem. Both alpha‐ and beta‐diversity indices were extended to Hill numbers to verify the contribution of abundant and rare taxa to DAR and DDR. The iCAMP approach was used to quantify the contribution of different ecological processes in structuring microbial communities. Results Strong spatial scaling patterns were observed for the whole communities and the rare subcommunities but only weak patterns for the abundant subcommunities. Rare subcommunities were mainly responsible for the observed spatial scaling patterns, as confirmed by extending spatial scaling diversity metrics to Hill numbers. Both environmental heterogeneity and local community assembly mechanisms drove the spatial scaling of microbial communities. Strong ecological drift and dispersal limitation underlay the spatial scaling of rare subcommunities, whereas high homogeneous selection weakened the spatial scaling of abundant subcommunities. Main Conclusions Rare taxa were mainly responsible for the biogeographic patterns followed by sediment microbial communities in the Beibu Gulf. Distinct ecological mechanisms underlay the different biogeographic patterns followed by abundant and rare subcommunities.

Environmental DNA metabarcoding reveals the influence of human activities on microeukaryotic plankton along the Chinese coastline - Zheng Zhang; Jiang Li; Hongjun Li; Linlin Wang; Yuqi Zhou; Shuzhen Li; Zhaojing Zhang; Kai Feng; Ye Deng (Water Research, 2023)

Sufentanil combined with parecoxib sodium inhibits proliferation and metastasis of HER2-positive breast cancer cells and regulates epithelial-mesenchymal transition - Sunmian Xu; Xiaohui Li; Wenbin Li; Nina Ma; Hongjun Ma; Jian Cui; Xiaogang You; Xuexin Chen (Clinical & Experimental Metastasis, 2023)

SIRT3/GLUT4 signaling activation by metformin protect against cisplatin-induced ototoxicity in vitro - Peiyu Du; Tianyi Liu; Pan Luo; Hejie Li; Wei Tang; Shimin Zong; Hongjun Xiao (Archives of Toxicology, 2023)

Facile construction of Z-scheme AgCl/Bi3TaO7 photocatalysts for effective removal of tetracycline under visible-light irradiation - Xiaoxin Guo; Jun Liu; Dan Li; Hongjun Cheng; Kankan Liu; Xiaoqing Liu; Tiansheng Liu (Environmental Science and Pollution Research, 2023)

Hydrochemical characteristics and quality assessment of groundwater in Guangxi coastal areas, China - Tengfei Fu; Chenzhe Li; Zhenyan Wang; Chen Qi; Guangquan Chen; Yushan Fu; Qiao Su; Xingyong Xu; Wenquan Liu; Hongjun Yu (Marine Pollution Bulletin, 2023)

Inhibitory effect and mechanism of a compound essential oils on Cladophora glomerata - Yanqun Wang; Dengyu Wang; Wenxi Zhao; Hongjun Liu; Li Li; Jie Bai (Marine Pollution Bulletin, 2023)

Developmental dynamics and survival characteristics of the common horse bot flies (Diptera, Gasterophilidae, Gasterophilus) in desert steppe - Ke Zhang; Zhongrui Ju; Yu Zhang; Chen Wang; Shalitanati Mubalake; Dini Hu; Dong Zhang; Kai Li; Hongjun Chu (Veterinary Parasitology, 2023)

Advances in technology and utilization of natural resources for achieving carbon neutrality and a sustainable solution to neutral environment - Saleem Raza; Ehsan Ghasali; Muslim Raza; Cheng Chen; Bisheng Li; Yasin Orooji; Hongjun Lin; Ceren Karaman; Hassan Karimi Maleh; Nevin Erk (Environmental Research, 2023)

Graphene oxide assisted assembly of superhydrophilic MOF-based membrane with 2D/3D hybrid nanochannels for enhanced water purification - Lingya Fei; Cheng Chen; Liguo Shen; Yuyao Zhang; Boya Wang; Jiujing Xu; Bisheng Li; Saleem Raza; Hongjun Lin (Chemical Engineering Journal, 2023)

Effects of shellfish culture on the community and mortality of zooplankton in a subtropical Bay - Bijian Pang; Hongjun Li; Mingmin Li; Xin Luo; Ying Chen; Tianshen Li; Wenlu Lan (Journal of Oceanology and Limnology, 2023)

Strontium isotopes in the Ordovician paleokarst reservoirs, Huanghua Depression, China - Jinning Zhang; Guomeng Han; Lixin Fu; Hongjun Li; Yuan Neng; Xiao Ma (Arabian Journal of Geosciences, 2023)

3D printing titanium dioxide-acrylonitrile-butadiene-styrene (TiO2-ABS) composite membrane for efficient oil/water separation - Lei Han; Liguo Shen; Hongjun Lin; Zhengyi Huang; Yanchao Xu; Renjie Li; Bisheng Li; Cheng Chen; Wei Yu; Jiaheng Teng (Chemosphere, 2023)

High propensity of membrane fouling and the underlying mechanisms in a membrane bioreactor during occurrence of sludge bulking - Mengfei Wu; Meijia Zhang; Liguo Shen; Xinhua Wang; Deng Ying; Hongjun Lin; Renjie Li; Yanchao Xu; Huachang Hong (Water Research, 2023)

Quality relationship between smoked and air-dried bacon of Sichuan-Chongqing in China: Free amino acids, volatile compounds, and microbial diversity - Li Yang; Hongjun Li; Han Wu; Chang Su; Zhifei He (Food Research International, 2023)

Dissimilatory manganese reduction facilitates synergistic cooperation of hydrolysis, acidogenesis, acetogenesis and methanogenesis via promoting microbial interaction during anaerobic digestion of waste activated sludge - Linli Wang; Yangyang Li; Xuesong Yi; Fei Yang; Dexin Wang; Hongjun Han (Environmental Research, 2023)

CircRNA3616 knockdown attenuates inflammation and apoptosis in spinal cord injury by inhibiting TLR4/NF-κB activity via sponging miR-137 - Li Wang; Zhiwen Song; Hongjun Zou; Haining Chen; Yong Hu; Xiangnan Li; Jinbo Liu (Molecular and Cellular Biochemistry, 2023)

Efficient oil-water emulsion treatment via novel composite membranes fabricated by CaCO3-based biomineralization and TA-Ti(IV) coating strategy - Hongli Xie; Binghong Chen; Hongjun Lin; Renjie Li; Liguo Shen; Genying Yu; Lining Yang (Science of The Total Environment, 2023)

Emissions of air pollutants from non-road construction machinery in Beijing from 2015 to 2019 - Xueyao Li; Liu Yang; Yongteng Liu; Chongbo Zhang; Xiaohong Xu; Hongjun Mao; Taosheng Jin (Environmental Pollution, 2023)

The coupling of persulfate activation and membrane separation for the effective pollutant degradation and membrane fouling alleviation - Mingzhu Zhou; Junjie Chen; Shuning Yu; Binghong Chen; Cheng Chen; Liguo Shen; Bisheng Li; Hongjun Lin (Chemical Engineering Journal, 2023)

CMC based microcapsules for smart delivery of pesticides with reduced risks to the environment - Ming Zhao; Zhenhai Chen; Li Hao; Huayao Chen; Xinhua Zhou; Hongjun Zhou (Carbohydrate Polymers, 2023)

The complete chloroplast genome of the medical plant Huperzia crispata from the Huperziaceae family: structure, comparative analysis, and phylogenetic relationships - Dengpan Yin; Bo Pang; Haibo Li; Qiao Liu; Yufeng Zhai; Nan Ma; Tongtong Chen; Hongjun Shen; Qiaojun Jia; Dekai Wang (Molecular Biology Reports, 2022)

Multi-Objective Optimization of Bioresorbable Magnesium Alloy Stent by Kriging Surrogate Model - Hongjun Wang; Li Jiao; Jie Sun; Pei Yan; Xibin Wang; Tianyang Qiu (Cardiovascular Engineering and Technology, 2022)

Microbial residues as the nexus transforming inorganic carbon to organic carbon in coastal saline soils - Pengshuai Shao; Tian Li; Kaikai Dong; Hongjun Yang; Jingkuan Sun (Soil Ecology Letters, 2022)

Aberrant brain connectivity is associated with childhood maltreatment in individuals with major depressive disorder - Qianyi Luo; Juran Chen; Yuhong Li; Zhiyao Wu; Xinyi Lin; Jiazheng Yao; Huiwen Yu; Huawang Wu; Hongjun Peng (Brain Imaging and Behavior, 2022)

Origin and Implications of Pollution in Coastal Groundwater of the Guangdong Province - Chenzhe Li; Tengfei Fu; Yushan Fu; Zhenyan Wang; Bin Li; Chen Qi; Guangquan Chen; Xingyong Xu; Hongjun Yu (Journal of Marine Science and Engineering, 2022)
The groundwater resource is crucial to the urbanization and industrialization in the Guangdong coastal area; the rapid development of Daya Bay has presented a challenge for the management of the groundwater quantity and quality. Therefore, a novel approach to hydrochemical analysis, which, combined with the health risk model and the water quality index (WQI), was used to explain the hydrochemistry characteristics and risks to human health of groundwater in the Guangdong coastal areas in addition to investigating the factors controlling groundwater quality. The results showed that the average concentration of total dissolved solids (TDS) in groundwater was 1935.26 mg/L and the quality of water was weakly alkaline. The dominant hydrochemical types of groundwater were identified to be Mg-HCO3 and Na-Cl·HCO3. The main factor influencing the hydrochemical composition was rock weathering, while the result of principal component analysis (PCA) shows seawater intrusion and anthropogenic inputs also have an effect on the water quality. The conclusions of the water quality assessment indicated that most of the groundwater samples were acceptable for drinking. However, both WQI and the non-carcinogenic hazard quotient (HQ) values indicated unacceptable risks in any area of Maoming, Zhanjiang and Shantou, and, according to the hazard index (HI) value, children in the study area are at more danger to health risks than adults. It is suggested that both groundwater salinization and nitrate pollution should be paid attention to when improving groundwater quality and exploring the sustainable utilization of groundwater resources.

Two-stage hybrid network for segmentation of COVID-19 pneumonia lesions in CT images: a multicenter study - Yaxin Shang; Zechen Wei; Hui Hui; Xiaohu Li; Liang Li; Yongqiang Yu; Ligong Lu; Li Li; Hongjun Li; Qi Yang; Meiyun Wang; Meixiao Zhan; et al. (Medical & Biological Engineering & Computing, 2022)

Distribution characteristics of delta reservoirs reshaped by bottom currents: A case study from the second member of the Yinggehai Formation in the DF1-1 gas field, Yinggehai Basin, South China Sea - Shuo Chen; Renhai Pu; Huiqiong Li; Hongjun Qu; Tianyu Ji; Siyu Su; Yunwen Guan; Hui Zhang (Acta Oceanologica Sinica, 2022)

How habitat heterogeneity shapes bacterial and protistan communities in temperate coastal areas near estuaries - Zelong Zhao; Hongjun Li; Yi Sun; Kuishuang Shao; Xiaocheng Wang; Xindong Ma; Anyi Hu; Haikun Zhang; Jinfeng Fan (Environmental Microbiology, 2022)
Summary In this study, we investigated microbial communities (bacteria and protist) in two coastal areas near the estuaries of the Liaohe (LH) River and Yalujiang (YLJ) River in the Northwestern Pacific Ocean. Due to the existence of Liaodong Peninsula and different levels of urbanization, geographical segregation and significant environmental heterogeneity were observed between these two areas. There were significantly different regional species pools and biogeographic patterns for both bacterial and protistan communities between LH and YLJ coastal areas. Species turnover was the main mechanism driving β‐diversity patterns of both bacterial and protistan communities in each area. In addition, the contributed ratio of nestedness to the β‐diversity patterns was significantly higher for protists compared to bacteria. Variation in regional species pools was found to be the dominant driver of differences of bacterial and protistan communities between the LH and YLJ coastal areas. For a single‐studied area, local community assembly mechanisms, including heterogeneous selection and dispersal limitation, were found to shape the bacterial and protistan communities through calculation of the β‐deviation index. Among them, the relative importance of heterogeneous selection and dispersal limitation on the community assembly varied according to microorganism type and habitat.

Multiple-Stage Mineralization in the Huayangchuan U−REE−Mo−Cu−Fe Ore Belt of the Qinling Orogen, Central China: Geological and Re−Os Geochronological Constraints - Hongjun Jiang; Chunsi Yang; Dequan Wang; Hui Zheng; Jie Li; Huayong Chen (Journal of Earth Science, 2022)
The Huayangchuan ore belt is located in the western segment of Xiaoqinling Orogen in the southern margin of the North China Craton (NCC), and hosts voluminous magmatism and significant U−REE−Mo−Cu−Fe polymetallic mineralization. However, geochronological framework of the various mineralization phases in this region is poorly understood. Here, we present new Re−Os isochron ages on magnetite from the Caotan Fe deposit (2 675 ± 410 Ma, MSWD = 0.55), and on pyrite from the Jialu REE deposit (2 127 ± 280 Ma, MSWD = 1.9) and Yuejiawa Cu deposit (418 ± 23 Ma, MSWD = 11.5), and Re−Os weighted average model age on pyrite from the Taoyuan Mo−U deposit (235 ± 14 Ma, MSWD = 0.17). These ages, combined with regional geology and mineralization ages from other deposits, suggest that mineralization in the Huayangchuan ore belt lasted from the Neoarchean to the Late Mesozoic. The mineralization corresponds to regional tectono-magmatic events, including the Neoar-chean alkali magmatism (REE mineralization), Paleoproterozoic plagioclase-amphibolite emplacement (Fe mineralization), Paleoproterozoic pegmatite magmatism (U mineralization), Paleozoic Shangdan oceanic slab subduction-related arc magmatism (Cu mineralization), Early Mesozoic Paleo-Tethys Ocean subduction-related arc magmatism (Mo−U mineralization), and Late Mesozoic Paleo-Pacific oceanic plate subduction direction change-related Mo(-Pb) mineralization. We proposed that the Huayang-chuan ore belt has undergone prolonged metallogenic evolution, and the magmatism and associated mineralization were controlled by regional geodynamic events.

The addition of sawdust reduced the emission of nitrous oxide in pig manure composting by altering the bacterial community structure and functions - Chao Liu; Jiao Yan; Qian Huang; Hongjun Liu; Cece Qiao; Rong Li; Biao Shen; Qirong Shen (Environmental Science and Pollution Research, 2022)

Stock Assessment of Hatchery-Released Clam Meretrix meretrix in an Estuary of China From the Perspectives of Population Ecology and Genetic Diversity - Anguo Zhang; Hongjun Li; Xiaolong Yang; Lili Wang; Yangchun Gao; Mingshan Song; Xiutang Yuan (Frontiers in Marine Science, 2021)
In this study, the release effects of the buried clam Meretrix meretrix in a northern estuary of China (Shuangtaizi Estuary) was assessed in terms of population ecology and genetic variability by using longer-term monitoring data from 2011 (used as the baseline data) to 2018. A total of 2.4 × 10 8 hatchery juveniles were released from 2012 to 2014, and follow-up monitoring survey of the growth, distribution, density, and biomass of M. meretrix population was carried out. Results showed a temporary spike in the population of M. meretrix , and the population underwent considerable year-to-year fluctuations in total abundance and biomass. Meanwhile, the age structure of the populations from 2011 to 2018 is still an unstable expanding type. Genetic analysis based on 10 polymorphic microsatellite markers revealed no significant genetic differentiation and weak genetic structures between years but higher genetic diversities in 2014–2018 than in the initial period (2013) of stock restoration. Our study suggests that effective policies for management and conservation to restore M. meretrix population by local governments are still needed in the long run.

Genomic selection to introgress exotic maize germplasm into elite maize in China to improve kernel dehydration rate - Hongjun Yong; Nan Wang; Xiaojun Yang; Fengyi Zhang; Juan Tang; Zhiyuan Yang; Xinzhe Zhao; Yi Li; Mingshun Li; Degui Zhang; Zhuanfang Hao; Jianfeng Weng; et al. (Euphytica, 2021)

Petrophysical Texture Heterogeneity of Vesicles in Andesite Reservoir on Micro-Scales - Mutian Qin; Shuyun Xie; Jianbo Zhang; Tianfu Zhang; Emmanuel John M. Carranza; Hongjun Li; Jiayi Ma (Journal of Earth Science, 2021)

Profiling of Serum Exosome MiRNA Reveals the Potential of a MiRNA Panel as Diagnostic Biomarker for Alzheimer’s Disease - Zhiwu Dong; Hongjun Gu; Qiang Guo; Shuang Liang; Jian Xue; Feng Yao; Xianglu Liu; Feifei Li; Huiling Liu; Li Sun; Kewen Zhao (Molecular Neurobiology, 2021)

Disrupted pathways from frontal-parietal cortex to basal ganglia and cerebellum in patients with unmedicated obsessive compulsive disorder as observed by whole-brain resting-state effective connectivity analysis – a small sample pilot study - Wei Liu; Minghui Hua; Jun Qin; Qiuju Tang; Yunyi Han; Hongjun Tian; Daxiang Lian; Zhengqing Zhang; Wenqiang Wang; Chunxiang Wang; Ce Chen; Deguo Jiang; et al. (Brain Imaging and Behavior, 2021)

Strong and regionally distinct links between ice‐retreat timing and phytoplankton production in the Arctic Ocean - Hongjun Song; Rubao Ji; Meibing Jin; Yun Li; Zhixuan Feng; Øystein Varpe; Cabell S. Davis (Limnology and Oceanography, 2021)
Recent rapid sea‐ice changes in the Arctic Ocean have been widely considered to alter phytoplankton bloom timing and primary production, but the magnitude and regionality of this effect remain unclear. Here, we examined the spatial patterns in bloom timing, bloom magnitude, and primary productivity in relation to ice‐retreat timing, using a combination of satellite observations and numerical modeling. We found distinct regional differences in how the phytoplankton bloom relates to ice‐retreat timing. In the Arctic shelf regions, earlier and stronger blooms follow earlier annual ice retreats and enhanced light availability. By contrast, in some parts of the central Arctic, especially in the Canada Basin, there have been weakened blooms and reduced primary production in recent years. This reduction is largely due to a chain reaction triggered by earlier ice‐melt and enhanced haline stratification, which further suppress vertical nutrient exchange and reduce surface nutrients in an already nutrient‐limited system. Recognizing and quantifying strong and regionally distinct links between sea‐ice retreat and primary production will improve spatiotemporal projections of biogeochemical cycles and trophic flows in Arctic marine ecosystems.

Strategies to solve the reverse inference fallacy in future MRI studies of schizophrenia: a review - Chuanjun Zhuo; Gongying Li; Xiaodong Lin; Deguo Jiang; Yong Xu; Hongjun Tian; Wenqiang Wang; Xueqin Song (Brain Imaging and Behavior, 2021)
Few advances in schizophrenia research have been translated into clinical practice, despite 60 years of serum biomarkers studies and 50 years of genetic studies. During the last 30 years, neuroimaging studies on schizophrenia have gradually increased, partly due to the beautiful prospect that the pathophysiology of schizophrenia could be explained entirely by the Human Connectome Project (HCP). However, the fallacy of reverse inference has been a critical problem of the HCP. For this reason, there is a dire need for new strategies or research “bridges” to further schizophrenia at the biological level. To understand the importance of research “bridges,” it is vital to examine the strengths and weaknesses of the recent literature. Hence, in this review, our team has summarized the recent literature (1995–2018) about magnetic resonance imaging (MRI) of schizophrenia in terms of regional and global structural and functional alterations. We have also provided a new proposal that may supplement the HCP for studying schizophrenia. As postulated, despite the vast number of MRI studies in schizophrenia, the lack of homogeneity between the studies, along with the relatedness of schizophrenia with other neurological disorders, has hindered the study of schizophrenia. In addition, the reverse inference cannot be used to diagnose schizophrenia, further limiting the clinical impact of findings from medical imaging studies. We believe that multidisciplinary technologies may be used to develop research “bridges” to further investigate schizophrenia at the single neuron or neuron cluster levels. We have postulated about future strategies for overcoming the current limitations and establishing the research “bridges,” with an emphasis on multimodality imaging, molecular imaging, neuron cluster signals, single transmitter biomarkers, and nanotechnology. These research “bridges” may help solve the reverse inference fallacy and improve our understanding of schizophrenia for future studies.

Evaluating Neurodevelopmental Consequences of Perinatal Exposure to Antiretroviral Drugs: Current Challenges and New Approaches - Jordan G. Schnoll; Brian Temsamrit; Daniel Zhang; Hongjun Song; Guo-li Ming; Kimberly M. Christian (Journal of Neuroimmune Pharmacology, 2021)

Distribution and Assessment of Cr, Pb, Ni and Cd in Topsoil of the Modern Yellow River Delta, China - Hongjun Yang; Jingkuan Sun; Jiangbao Xia; Zhanyong Fu; Shuai Cheng; Tian Li; Pengshuai Shao; Kaikai Dong; Jinzhao Ma; Lu Feng (Wetlands, 2021)

Multi-scaling Properties of 2D Reservoir Micro-pore Heterogeneity Based on Digital Casting Thin-Section Images - Lihong Zhou; Mutian Qin; Dunqing Xiao; Chongbiao Leng; Hongjun Li; Shuyun Xie; E. J. M. Carranza; Jinning Zhang (Natural Resources Research, 2021)

Comparative analysis of H3K4 and H3K27 trimethylations in two contrasting Tibetan hulless barely varieties on powdery mildew infection - Sang Zha; Chunbao Yang; Xingquan Zeng; Zeqing Li; Yulin Wang; Hongjun Yuan; Mingzhai Yu; Qijun Xu (Journal of Plant Pathology, 2021)

Characteristics and origins of middle Miocene mounds and channels in the northern South China Sea - Yufeng Li; Gongcheng Zhang; Renhai Pu; Hongjun Qu; Huailei Shen; Xueqin Zhao (Acta Oceanologica Sinica, 2021)

Update on recommendations for the diagnosis and treatment of SARS-CoV-2 infection in children - Hongjun Miao; Han Li; Yinying Yao; Mingfu Wu; Chao Lu; Jun Wang; Man Tian; Ying Li; Peiliang Luo; Jianhui Gu; Bin Yuan; Shouchuan Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
Since the outbreak of novel coronavirus infection pneumonia in Wuhan City, China, in late 2019, such cases have been gradually reported in other parts of China and abroad. Children have become susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) because of their immature immune function. As the outbreak has progressed, more cases of novel coronavirus infection/pneumonia in children have been reported. Compared with adults, the impact of SARS-CoV-2 infection in children is less severe, with a lower incidence and susceptibility in children, which results in fewer children being tested, thereby underestimating the actual number of infections. Therefore, strengthening the diagnosis of the disease is particularly important for children, and early and clear diagnosis can determine treatment strategies and reduce the harm caused by the disease to children. According to the Novel Coronavirus Infection Pneumonia Diagnosis and Treatment Standards ( trial version 7 ) issued by National Health Committee and the latest diagnosis and treatment strategies for novel coronavirus infection pneumonia in children, this review summarizes current strategies on diagnosis and treatment of SARS-CoV-2 infection in children.

Differences in functional connectivity density among subtypes of schizophrenic auditory hallucination - Chuanjun Zhuo; Gongying Li; Feng Ji; Ce Chen; Deguo Jiang; Xiaodong Lin; Yong Xu; Hongjun Tian; Lina Wang; Chunhua Zhou; Xiao Lin (Brain Imaging and Behavior, 2020)

Common and distinct global functional connectivity density alterations in patients with bipolar disorder with and without auditory verbal hallucination during major depressive episodes - Lixue Qiu; Jaen Ye; Feng Ji; Gang Li; Gongying Li; Xiaoyan Ma; Ranli Li; Hongjun Tian; Lina Wang; Guangdong Chen; Yong Xu; Wenqiang Wang; et al. (Brain Imaging and Behavior, 2020)

Optimization of porcine embryonic germ cell culture system - Yang Li; Yu Qiao; Fei Li; Hongjun Wang; Xiao Dong (In Vitro Cellular & Developmental Biology - Animal, 2020)

Modeling of power sector decarbonization in China: comparisons of early and delayed mitigation towards 2-degree target - Huan Wang; Wenying Chen; Hongjun Zhang; Nan Li (Climatic Change, 2020)

A new permeability predictive model based on NMR data for sandstone reservoirs - Hongjun Xu; Changxi Li; Yiren Fan; Falong Hu; Jun Yu; Jinyu Zhou; Changxue Wang; Chunmei Yang (Arabian Journal of Geosciences, 2020)

A longitudinal study of brain volume changes in rhesus macaque model infected with SIV - Bonan Song; Yunfang Li; Jiaojiao Liu; Haifeng Mi; Dan Liu; Wei Wang; Jun Sun; Yuanyuan Wang; Hongjun Li (Journal of NeuroVirology, 2020)

Comprehensive Investigation and Assessment of Nutrient and Heavy Metal Contamination in the Surface Water of Coastal Bohai Sea in China - Heshan Lin; Hongjun Li; Xiaolong Yang; Zizhou Xu; Yindong Tong; Xingguang Yu (Journal of Ocean University of China, 2020)

Advances of Four Machine Learning Methods for Spatial Data Handling: a Review - Peijun Du; Xuyu Bai; Kun Tan; Zhaohui Xue; Alim Samat; Junshi Xia; Erzhu Li; Hongjun Su; Wei Liu (Journal of Geovisualization and Spatial Analysis, 2020)

Karstification of Ordovician carbonate reservoirs in Huanghua depression and its control factors - Jinning Zhang; Jiansheng Zhou; Lixin Fu; Hongjun Li; Da Lou (Carbonates and Evaporites, 2020)
With extensive ancient karsts and abundant oil and gas resources, the Ordovician carbonate reservoirs in the Huanghua depression have broad prospects of exploration and development. The types, characteristics, distribution and controlling factors of karsts were investigated by means of the analysis of cores, thin slices, logging, seismic, and geochemical data in this study. The study reveals that the Ordovician carbonate reservoirs in the Huanghua depression falls into three main categories, pore type, pore-vug-fracture type and fracture type, of which, pore-vug-fracture reservoirs account for 62%. The epigenetic uniform karst mainly developed in the Late Ordovician to Early Carboniferous, while the differential karst developed in the Mesozoic. The uniform karstification mainly include chemical dissolution of the original carbonate rock, while the differential karstification not only include chemical dissolution but also hydraulic erosion and biochemical dissolution by organic acid. The burial karstification mainly involved the dissolution of the Ordovician reservoir by large amount of acidic fluids generated by the overlying Upper Paleozoic coal measure source rock while generating hydrocarbon. The dissolution caused by upwelling magmatic-tectonic hydrothermal fluids along faults also contributed to the formation of burial karst reservoirs. The sedimentation-diagenesis and paleogeomorphology-tectonic movement have certain control effects on the karstification of the Ordovician reservoirs in the Huanghua depression, determining the reservoir quality.

Biofertilizer application triggered microbial assembly in microaggregates associated with tomato bacterial wilt suppression - Menghui Dong; Mengli Zhao; Zongzhuan Shen; Xuhui Deng; Yannan Ou; Chengyuan Tao; Hongjun Liu; Rong Li; Qirong Shen (Biology and Fertility of Soils, 2020)

Effect of five modified mass selection cycles on combining ability in two Chinese maize populations - Hongjun Yong; Juan Tang; Xinzhe Zhao; Fengyi Zhang; Zhiyuan Yang; Yi Li; Mingshun Li; Degui Zhang; Zhuanfang Hao; Jianfeng Weng; Jienan Han; Bo Peng; et al. (Euphytica, 2020)

Magnesium alleviates aluminum toxicity by promoting polar auxin transport and distribution and root alkalization in the root apex in populus - Zhen Zhang; Dunyi Liu; Hongjun Meng; Shengting Li; Shufeng Wang; Zhongchun Xiao; Juanjuan Sun; Longran Chang; Keming Luo; Nannan Li (Plant and Soil, 2020)

Phylodynamic analysis of two amino acid substitutions in the hemagglutinin protein of canine distemper virus strains detected in fur-bearing animals in China - Rongshan Tao; Hengxing Ba; Jie Chen; Mengjia Liu; Hongjun Pan; Xue Li; Quankai Wang; Jianjun Zhao (Virus Genes, 2020)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Physiological, genomic and transcriptomic comparison of two Brassica napus cultivars with contrasting cadmium tolerance - Shufeng Wang; Juanjuan Sun; Shengting Li; Kun Lu; Hongjun Meng; Zhongchun Xiao; Zhen Zhang; Jiana Li; Feng Luo; Nannan Li (Plant and Soil, 2019)

Enzyme and pH dual-responsive avermectin nano-microcapsules for improving its efficacy - Guanghua Liu; Guanquan Lin; Xida Lin; Hongjun Zhou; Huayao Chen; Li Hao; Xinhua Zhou (Environmental Science and Pollution Research, 2019)

Fine mapping of the wheat powdery mildew resistance gene Pm52 using comparative genomics analysis and the Chinese Spring reference genomic sequence - Peipei Wu; Jinghuang Hu; Jingwei Zou; Dan Qiu; Yunfeng Qu; Yahui Li; Teng Li; Hongjun Zhang; Li Yang; Hongwei Liu; Yang Zhou; Zhongjun Zhang; et al. (Theoretical and Applied Genetics, 2019)

Control of NOx emissions by air staging in small- and medium-scale biomass pellet boilers - Yuening Li; Yingchao Lin; Jingbo Zhao; Boyang Liu; Ting Wang; Peng Wang; Hongjun Mao (Environmental Science and Pollution Research, 2019)

Altered voxel-wise gray matter structural brain networks in schizophrenia: Association with brain genetic expression pattern - Feng Liu; Hongjun Tian; Jie Li; Shen Li; Chuanjun Zhuo (Brain Imaging and Behavior, 2019)

Low-frequency fluctuation characteristics in rhesus macaques with SIV infection: a resting-state fMRI study - Jing Zhao; Feng Chen; Meiji Ren; Li Li; Aixin Li; Bin Jing; Hongjun Li (Journal of NeuroVirology, 2019)

Breeding potential of inbred lines derived from five maize (Zea mays L.) populations - Hongjun Yong; Fengyi Zhang; Juan Tang; Zhiyuan Yang; Xinzhe Zhao; Mingshun Li; Degui Zhang; Zhuanfang Hao; Jianfeng Weng; Xinhai Li (Euphytica, 2019)

The concurrent effects of the South Asian monsoon and the plateau monsoon over the Tibetan Plateau on summer rainfall in the Tarim Basin of China - Yong Zhao; Xiaojing Yu; Junqiang Yao; Xinning Dong; Hongjun Li (International Journal of Climatology, 2019)
Based on the observed rainfall data at 34 stations over the Tarim Basin (TB) and the National Centers for Environmental Prediction/National Center for Atmospheric Research reanalysis data during 1961–2012, the concurrent effects of the plateau monsoon (PM) over the Tibetan Plateau and the South Asian monsoon (SAM) on summer rainfall over the TB are investigated. Mid‐upper tropospheric temperature (MUTT) plays an important role in linking the PM and the SAM with summer rainfall over the TB. The concurrent influential mechanisms of the PM and the SAM on summer rainfall over the TB can be summarized as follows. The strengthened (weakened) PM and the weakened (strengthened) SAM cause mid‐upper tropospheric cooling (warming), which tends to result in the migration of the subtropical westerly jet further southward (northward). Then an anomalous southerly (northerly) flow prevails over the TB, and more (less) water vapour is transported into the TB by a two‐step process. All above contribute significantly to an increase (decrease) in the occurrence of summer rainfall over the TB. In addition, we also discuss the relative contribution of the PM and the SAM to summer rainfall over the TB. Partial correlations show that the PM and the SAM can both individually influence summer rainfall over the TB. The PM has a direct effect on summer rainfall over the TB, for its considerable relations not only with MUTT but also with atmospheric circulation. Whereas the SAM has an indirect effect for its only influence on MUTT, which then give rise to an anomalous circulation related to summer rainfall over the TB.

A non-negative and high-resolution finite volume method for the depth-integrated solute transport equation using an unstructured triangular mesh - Ronghui Ye; Chenming Zhang; Jun Kong; Guangqiu Jin; Hongjun Zhao; Zhiyao Song; Ling Li (Environmental Fluid Mechanics, 2018)

Population genetic patterns of the solitary tunicate, Molgula manhattensis, in invaded Chinese coasts: large-scale homogeneity but fine-scale heterogeneity - Yiyong Chen; Shiguo Li; Yaping Lin; Hongjun Li; Aibin Zhan (Marine Biodiversity, 2018)

Projected changes in the annual cycle of precipitation over central Asia by CMIP5 models - Xiaojing Yu; Yong Zhao; Xiaojiao Ma; Junqiang Yao; Hongjun Li (International Journal of Climatology, 2018)
Future changes in the annual cycle of the precipitation in central Asia (CA) were estimated based on the historical and representative concentration pathway 8.5 (RCP8.5) experiments from 25 models of the Coupled Model Intercomparison Project phase 5. Compared with the Global Precipitation Climatology Project observations, the historical (1979–1999) experiments showed that most models can capture the migration of rainfall centres, but remarkable discrepancies exist in the location and intensity of rainfall centres between simulations and observations. Considering the skill scores of precipitation and pattern correlations of circulations, which are closely related to the precipitation for each month, for the 25 models, the four best models (e.g., CanESM2, CMCC‐CMS, MIROC5 and MPI‐ESM‐LR) with relatively good performance were selected. The four models' ensemble mean indicated that the migration and location of the precipitation centres were better reproduced, except the intensity of the centres was overestimated, compared with the result that only took the precipitation into consideration. Based on the four best models' ensemble mean under RCP8.5 scenarios, precipitation was projected to increase dramatically over most of the CA region in the boreal cold seasons (November, December, January, February, March and April) and May, with the maximum in December at the end of 21st century (2079–2099), and several positive centres were located in the Pamirs Plateau, the Tianshan Mountains and the northern Himalayas. The precipitation changes were weak in the boreal warm seasons (June, July, August, September and October), with a dry centre located in the Pamirs Plateau and a wet centre in the northern Himalayas. These projected changes can be directly attributed to the overlay of anomalous moisture convergence and evaporation, and other possible mechanisms of dynamic and thermodynamic factors need to be further elucidated.

Pm61: a recessive gene for resistance to powdery mildew in wheat landrace Xuxusanyuehuang identified by comparative genomics analysis - Huigai Sun; Jinghuang Hu; Wei Song; Dan Qiu; Lei Cui; Peipei Wu; Hongjun Zhang; Hongwei Liu; Li Yang; Yunfeng Qu; Yahui Li; Teng Li; et al. (Theoretical and Applied Genetics, 2018)

Altered cerebro-cerebellum resting-state functional connectivity in HIV-infected male patients - Huijuan Wang; Ruili Li; Yawen Zhou; Yanming Wang; Jin Cui; Benedictor Alexander Nguchu; Bensheng Qiu; Xiaoxiao Wang; Hongjun Li (Journal of NeuroVirology, 2018)

Study on the Combined Application of CFAR and Deep Learning in Ship Detection - Ruifu Wang; Jie Li; Yaping Duan; Hongjun Cao; Yingjie Zhao (Journal of the Indian Society of Remote Sensing, 2018)

A New Approach of Rpf Addition to Explore Bacterial Consortium for Enhanced Phenol Degradation Under High Salinity Conditions - Ziqiao Li; Yunge Zhang; Yuyang Wang; Rongwu Mei; Yu Zhang; Muhammad Zaffar Hashmi; Hongjun Lin; Xiaomei Su (Current Microbiology, 2018)

Construction and verification of a unified p–y curve for laterally loaded piles - Hongjiang Li; Liyuan Tong; Songyu Liu; Hongjun Liu; Mingfei Zhang (Bulletin of Engineering Geology and the Environment, 2018)

Oil mixing behavior after an oil spill: identification conflicts of different fingerprints - Shijie He; Hongjun Yu; Yongming Luo; Chuanyuan Wang; Xueshuang Li; Zhongping Li (Environmental Science and Pollution Research, 2018)

Continuous application of different organic additives can suppress tomato disease by inducing the healthy rhizospheric microbiota through alterations to the bulk soil microflora - Hongjun Liu; Wu Xiong; Ruifu Zhang; Xinnan Hang; Dongsheng Wang; Rong Li; Qirong Shen (Plant and Soil, 2018)

The impact of modern plant breeding on dominant Chinese wheat cultivars (Triticum aestivum L.) revealed by SSR and functional markers - Lingzhi Meng; Chao Xiang; Hongwei Liu; Li Yang; Chunyan Mai; Liqiang Yu; Yunliang Wei; Hongjie Li; Hongjun Zhang; Yang Zhou (Genetic Resources and Crop Evolution, 2018)

The responses of two native plant species to soil petroleum contamination in the Yellow River Delta, China - Wenjun Xie; Yanpeng Zhang; Rui Li; Hongjun Yang; Tao Wu; Liping Zhao; Zhaohua Lu (Environmental Science and Pollution Research, 2017)

The Impact of Impoundment on Mercury Bioaccumulation in Fish Downstream from a Newly Constructed Reservoir, Wujiang River, Southwest China - Sixin Li; Lianfeng Zhou; Jianbo Chang; Zhi Yang; Juxiang Hu; Wang Hongjun (Archives of Environmental Contamination and Toxicology, 2017)

Development and Application of Urban High Temporal-Spatial Resolution Vehicle Emission Inventory Model and Decision Support System - Yi Zhang; Lin Wu; Chao Zou; Boyu Jing; Xiaoyu Li; Tim Barlow; Turpin Kevin; Michel André; Yao Liu; Peipei Ren; Gongdong Wang; Hongjun Mao (Environmental Modeling & Assessment, 2017)

Breeding potential of maize germplasm populations to improve yield and predominant heterotic pattern in Northeast China - Hongjun Yong; Zhenguo Jin; Li Gao; Lin Zhang; Xianjun Liu; Fangjun Zhang; Xiaocong Zhang; Degui Zhang; Mingshun Li; Jianfeng Weng; Zhuanfang Hao; Shihuang Zhang; et al. (Euphytica, 2017)

Occurrence of submarine canyons, sediment waves and mass movements along the northern continental slope of the South China Sea - Hongjun Chen; Wenhuan Zhan; Liqing Li; Ming-ming Wen (Journal of Earth System Science, 2017)

De novo assembly, gene annotation, and molecular marker development using Illumina paired-end transcriptome sequencing in the clam Saxidomus purpuratus - Hongjun Li; Min Liu; Sheng Ye; Feng Yang (Genes & Genomics, 2017)

Analysis of the genetic architecture of maize ear and grain morphological traits by combined linkage and association mapping - Chaoshu Zhang; Zhiqiang Zhou; Hongjun Yong; Xiaochong Zhang; Zhuanfang Hao; Fangjun Zhang; Mingshun Li; Degui Zhang; Xinhai Li; Zhenhua Wang; Jianfeng Weng (Theoretical and Applied Genetics, 2017)

MCP1 triggers monocyte dysfunctions during abnormal osteogenic differentiation of mesenchymal stem cells in ankylosing spondylitis - Zhongyu Xie; Peng Wang; Jinteng Li; Yuxi Li; Shan Wang; Xiaohua Wu; Suhe Sun; Shuizhong Cen; Hongjun Su; Wen Deng; Zhenhua Liu; Yi Ouyang; et al. (Journal of Molecular Medicine, 2017)

Heterosis and combining ability of seven maize germplasm populations - Xiaocong Zhang; Hongjun Yong; Zhiqiang Zhou; Chaoshu Zhang; Ming Lu; Qi Sun; Lin Zhang; Mingshun Li; Degui Zhang; Jianfeng Weng; Zhuanfang Hao; Shihuang Zhang; et al. (Euphytica, 2017)

Fine mapping of a quantitative trait locus conferring resistance to maize rough dwarf disease - Changlin Liu; Jinge Hua; Chang Liu; Degui Zhang; Zhuanfang Hao; Hongjun Yong; Chuanxiao Xie; Mingshun Li; Shihuang Zhang; Jianfeng Weng; Xinhai Li (Theoretical and Applied Genetics, 2016)

Molecular variation and expansion of a rice black-streaked dwarf virus population based on analysis of segment 1 in Jining, China - Yu Zhou; Qingchang Meng; Yanping Chen; Jirong Wu; Zhuanfang Hao; Zhenhua Wang; Degui Zhang; Mingshun Li; Hongjun Yong; Shihuang Zhang; Xinhai Li; Jianfeng Weng (Archives of Virology, 2016)

Distinct Hippocampal Expression Profiles of lncRNAs in Rats Exhibiting a PTSD-like Syndrome - Liu Qingzhen; Ma Jiehua; Yu Zhiyang; Liu Hongjun; Chen Chunlong; Li Weiyan (Molecular Neurobiology, 2016)

Efficacy and safety of quetiapine extended release monotherapy in bipolar depression: a multi-center, randomized, double-blind, placebo-controlled trial - Huafang Li; Niufan Gu; Hongyan Zhang; Gang Wang; Qingrong Tan; Fude Yang; Yuping Ning; Honggeng Zhang; Zheng Lu; Xiufeng Xu; Jianguo Shi; Chengge Gao; et al. (Psychopharmacology, 2016)

Longitudinal assessment of fractional anisotropy alterations caused by simian immunodeficiency virus infection: a preliminary diffusion tensor imaging study - Zhenchao Tang; Enqing Dong; Jiaojiao Liu; Zhenyu Liu; Wenjuan Wei; Bo Wang; Hongjun Li; Jie Tian (Journal of NeuroVirology, 2016)

Evaluation of diagnostic ratios of medium and serious weathered oils from five different oil sources - Shijie He; Chuanyuan Wang; Yantai Li; Hongjun Yu; Bin Han (Acta Oceanologica Sinica, 2016)

Trade-off between seed defensive traits and impacts on interaction patterns between seeds and rodents in forest ecosystems - Zhibin Zhang; Zhenyu Wang; Gang Chang; Xianfeng Yi; Jiqi Lu; Zhishu Xiao; Hongmao Zhang; Lin Cao; Fusheng Wang; Hongjun Li; Chuan Yan (Plant Ecology, 2016)

A pilot fMRI study of the effect of stressful factors on the onset of depression in female patients - Gongying Li; Xiaoyan Ma; Haiman Bian; Xinhai Sun; Ning Zhai; Mengyuan Yao; Hongru Qu; Shengzhang Ji; Hongjun Tian; Chuanjun Zhuo (Brain Imaging and Behavior, 2016)

Optimization of culture conditions for porcine embryonic germ cells - Xiao Dong; Yang Li; Hongjun Wang (In Vitro Cellular & Developmental Biology - Animal, 2016)

The potential geographic distribution of Bactrocera correcta (Diptera: Tephrididae) in China based on eclosion rate model - Yujia Qin; Wenlong Ni; Jiajiao Wu; Zihua Zhao; Hongjun Chen; Zhihong Li (Applied Entomology and Zoology, 2015)

In vivo construction of tissue-engineered cartilage using adipose-derived stem cells and bioreactor technology - Hongjun Kang; Shibi Lu; Jiang Peng; Qiang Yang; Shuyun Liu; Li Zhang; Jingxiang Huang; Xiang Sui; Bin Zhao; Aiyuan Wang; Wenjing Xu; Quanyi Guo; et al. (Cell and Tissue Banking, 2015)

Grey matter volume abnormalities in patients with bipolar I depressive disorder and unipolar depressive disorder: a voxel-based morphometry study - Yi Cai; Jun Liu; Li Zhang; Mei Liao; Yan Zhang; Lifeng Wang; Hongjun Peng; Zhong He; Zexuan Li; Weihui Li; Shaojia Lu; Yuqiang Ding; et al. (Neuroscience Bulletin, 2015)

Development and characterization of 13 polymorphic microsatellite markers for the Chinese surf clam (Mactra chinensis) through Illumina paired-end sequencing - Hongjun Li; Jingjing Zhang; Hongbo Li; Xianggang Gao; Chongbo He (Conservation Genetics Resources, 2014)

Glial Cell-Derived Neurotrophic Factor Attenuates Neuropathic Pain in a Mouse Model of Chronic Constriction Injury: Possible Involvement of E-cadherin/p120ctn Signaling - Cunjin Wang; Hongjun Wang; Jun Pang; Li Li; Suming Zhang; Ge Song; Na Li; Junping Cao; Licai Zhang (Journal of Molecular Neuroscience, 2014)

NCAM Signaling Mediates the Effects of GDNF on Chronic Morphine-Induced Neuroadaptations - Li Li; Junping Cao; Suming Zhang; Cunjin Wang; Jinfeng Wang; Ge Song; Hongjun Wang; Licai Zhang (Journal of Molecular Neuroscience, 2014)

Isolation and characterization of microsatellite loci from Gasterophilus pecorum (Diptera: Gasterophilidae) - Fang Cheng; Jianmei Yang; Dong Zhang; Defu Hu; Hongjun Chu; Jie Cao; Feng Jiang; Lan Bu; Kai Li (Conservation Genetics Resources, 2014)

Relationships between the West Asian subtropical westerly jet and summer precipitation in northern Xinjiang - Yong Zhao; MinZhong Wang; AnNing Huang; HongJun Li; Wen Huo; Qing Yang (Theoretical and Applied Climatology, 2014)

On the Fourier approximation method for steady water waves - Hongjun Zhao; Zhiyao Song; Ling Li; Jun Kong (Acta Oceanologica Sinica, 2014)

Characterization of 10 polymorphic microsatellite markers for Mediterranean blue mussel Mytilus galloprovincialis by EST database mining and cross-species amplification - HONGJUN LI; YU LIANG; LIJUN SUI; XIANGGANG GAO; CHONGBO HE (Journal of Genetics, 2013)

Breeding potential of U.S. maize germplasm for utilization in Chinese temperate conditions - Hongjun Yong; Xiaocong Zhang; Degui Zhang; Jianjun Wang; Huanxin Zhang; Mingshun Li; Wenguo Liu; Jianfeng Weng; Zhuanfang Hao; Xiaoke Ci; Li Bai; Xinhai Li; et al. (Euphytica, 2013)

Short-term impact of reservoir impoundment on the patterns of mercury distribution in a subtropical aquatic ecosystem, Wujiang River, southwest China - Sixin Li; Lianfeng Zhou; Hongjun Wang; Meihua Xiong; Zhi Yang; Juxiang Hu; Youguang Liang; Jianbo Chang (Environmental Science and Pollution Research, 2013)

On the universal third order Stokes wave solution - ZhiYao Song; HongJun Zhao; Ling Li; GuoNian Lü (Science China Earth Sciences, 2013)

Intracellular Cu/Zn superoxide dismutase (Cu/Zn-SOD) from hard clam Meretrix meretrix: its cDNA cloning, mRNA expression and enzyme activity - Xianggang Gao; Chongbo He; Hong Liu; Hongjun Li; Dan Zhu; Shengli Cai; Ying Xia; Ying Wang; Zhe Yu (Molecular Biology Reports, 2012)

Development and Linkage Analysis of 104 New Microsatellite Markers for Bay Scallop (Argopecten irradians) - Hongjun Li; Xiao Liu; Guofan Zhang (Marine Biotechnology, 2012)

Reconstructions of annual summer precipitation and temperature in north-central China since 1470 AD based on drought/flood index and tree-ring records - Liang Yi; Hongjun Yu; Junyi Ge; Zhongping Lai; Xingyong Xu; Li Qin; Shuzhen Peng (Climatic Change, 2012)

Major histocompatibility complex class IIA and IIB genes of the spotted halibut Verasper variegatus: genomic structure, molecular polymorphism, and expression analysis - Hongjun Li; Lianxin Jiang; Jiabo Han; Hao Su; Qing Yang; Chongbo He (Fish Physiology and Biochemistry, 2011)

Identification of Differentially Expressed Genes in Lung Tissues of Nickel-Exposed Rats Using Suppression Subtractive Hybridization - Jing Zhang; Jun Zhang; Yingying Fan; Lihong Liu; Mengjie Li; Yang Zhou; Zhihua Shao; Hongjun Shi; Ying Wang (Biological Trace Element Research, 2011)

Crop classification using MODIS NDVI data denoised by wavelet: A case study in Hebei Plain, China - Shengwei Zhang; Yuping Lei; Liping Wang; Hongjun Li; Hongbin Zhao (Chinese Geographical Science, 2011)

Histochemical and enzyme-histochemical studies of Oncomelania hupensis (Gredler, 1881), the intermediate host of Schistosoma japonicum - Wei Wang; Jianrong Dai; Hongjun Li; Yousheng Liang (Acta Parasitologica, 2011)
The distribution of glycogen, DNA and histone, and localization of activity of ten enzymes such as glucose-6-phosphatase (G-6-Pase), cytochrome oxidase (CCO), lactate dehydrogenase (LDH), 5′-nucleotidase (5′-NT), succinate dehydrogenase (SDH), glucose-6-phosphate dehydrogenase (G-6-PDH), alkaline phosphatase (ALP), acid phosphatase (ACP), Mg2+-adenosine triphosphatase (Mg2+-ATPase), and cholinesterase (CHE) in Oncomelania hupensis (Gredler, 1881) snails, the intermediate host of Schistosoma japonicum, was surveyed using the histochemical and enzyme-histochemical techniques. The results showed that the glycogen with high activity was widely distributed in snails. DNA showed its strongest reaction in testis. The histone was distributed in sites of the radula, parenchyma of penis and ovary. LDH and SDH were widely distributed in snails and all were abundant. Sites of the strongest enzyme activities of G-6-PDH were evident in the reproductive system together with central ganglia. Only the ovary showed a strong enzyme activity of G-6-Pase. Most tissues and organs contained CCO, and the activity of this enzyme was very strong. 5′-NT showed a strong enzyme activity in the ovary and testis. Mg2+-ATPase was localized in sites of the liver, stomach and reproductive gland. A strong enzyme activity of ALP appeared in the digestive system. ACP showed a low activity in snails. The central ganglia, nervous stem, liver, branchial duct, epithelia of the head and foot regions showed a very strong enzyme activity of CHE. The findings could provide a theoretical basis for development of highly effective molluscicides with low toxicity to other biota, as well as means for novel snail control strategies.

Mining single nucleotide polymorphisms from EST data of hard clam Meretrix meretrix - Hongjun Li; Dan Zhu; Xianggang Gao; Yun-feng Li; Jian Wang; Chongbo He (Conservation Genetics Resources, 2010)

An extended time-dependent numerical model of the mild-slope equation with weakly nonlinear amplitude dispersion - Hongjun Zhao; Zhiyao Song; Fumin Xu; Ruijie Li (Acta Oceanologica Sinica, 2010)

Feeding habits and habitats preferences affecting mercury bioaccumulation in 37 subtropical fish species from Wujiang River, China - Sixin Li; Lianfeng Zhou; Hongjun Wang; Youguang Liang; Jianbo Chang; Meihua Xiong; Yichao Zhang; Juxiang Hu (Ecotoxicology, 2009)

Feeding habits and habitats preferences affecting mercury bioaccumulation in 37 subtropical fish species from Wujiang River, China - Sixin Li; Lianfeng Zhou; Hongjun Wang; Youguang Liang; Juxiang Hu; Jianbo Chang (Ecotoxicology, 2009)

Association of North Atlantic Oscillations with Aksu River runoff in China - Hongjun Li; Zhihong Jiang; Qing Yang (Journal of Geographical Sciences, 2009)

Effects of niclosamide on Oncomelania hupensis, the intermediate snail host of Schistosoma japonicum: an enzyme-histochemical study - Wei Wang; Hongjun Li; Yousheng Liang; Jianrong Dai (Acta Parasitologica, 2009)
An enzyme-histochemical study of five enzymes, namely succinate dehydrogenase (SDH), lactate dehydrogenase (LDH), cytochrome oxidase (CCO), cholinesterase (CHE) and nitric oxide synthase (NOS), was elucidated in the soft tissues of Oncomelania hupensis, the intermediate host snail of Schistosoma japonicum, before and after the treatment with a suspension concentrate of niclosamide (SCN). Following the treatment of SCN, a marked loss occurred in the activity of the five enzymes mentioned above. LDH and SDH showed their strongest activity in the buccal mass and muscular fibers, CCO in buccal mass and liver, CHE in pellicle and ganglia, and NOS in muscular fibers and pharyngeal canal. The results indicate that SCN impairs the activities of the enzymes influencing the transfer of neurotransmitter and energy supply in O. hupensis, ultimately leading to the loss of various physiological functions, which is considered to be a cause of death in O. hupensis.